Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Beyond direct pathway engineering: reprogramming Fusarium fujikuroi from a GA3 producer into a GA4+7 factory - Hang Xiao; Tao-Xu Lu; Ming-Han Li; Ya-Ling Yi; Hao-Yang Li; Yu-Ke Cen; Zhi-Qiang Liu; Yug-Guo Zheng (Bioresource Technology, 2026)

New variant in KITLG shapes the pathogenesis of familial progressive hyper- and hypo-pigmentation - Bodan Wu; Ming He; Tongyun Liu; Wenjing Zhao; Jianhong Ye; Tao Jiang; Congcong Teng; Yaxin Huang; Yangjia Zhang; Jiao Li; Hong Shi; Jie Zhang (Molecular Genetics and Genomics, 2026)

Epigenetic silencing of DLEC1 correlates with tumor immune microenvironment and predicts immunotherapy prognosis in multiple cancers - Ruijie Ming; Qi Xiong; Shuh-Ying Tan; Lili Li; Shujie Bao; Jianhua Wang; Lijuan Zhao; Xiaoqian He; Zeze Zheng; Yan Wang; Xiaoyu Liu; Jun Tang; et al. (Human Genetics, 2026)
Cancer remains a major health issue globally, with increasing incidence and mortality rates. While immunotherapy has revolutionized cancer treatment, not all patients benefit, urging the identification of predictive biomarkers. This study utilized public datasets and tumor samples to examine the expression and promoter hypermethylation of DLEC1 in normal and tumor tissues, to evaluate its potential as prognostic and immunotherapy marker. In vitro and in vivo experiments on breast cancer (BrCa) cell lines were conducted to explore the functions and mechanisms of DLEC1 . The prognostic significance of DLEC1 downregulation and its impact on immune cell infiltration and immunotherapy efficacy were analyzed using the GEO and TCGA databases. DLEC1 was frequently downregulated and methylated across multiple cancers. In BrCa, expression of DLEC1 inhibited tumor cell proliferation, induced apoptosis, and activated the interferon lambda1 signaling pathway, indicating its important role as a bona fide tumor suppressor and immunoregulator. High DLEC1 expression correlated with better prognosis in several cancer types and with increased immune cell infiltration. Cancer patients with high DLEC1 expression showed improved overall and progression-free survival under immune checkpoint inhibitor therapies, such as anti-CTLA4, anti-PD1 and anti-PDL1. DLEC1 promoter hypermethylation is a promising biomarker for cancer prognosis and potential immunotherapy response prediction. Its expression and promoter hypermethylation status could thus help to guide clinical treatment strategies for cancer patients, particularly of breast cancer.

Breaking barriers in rice chlorophyll retrieval from satellite imagery: Mitigating row structure and saturation effects via RiceGORT and chlorophyll sensitivity enhancement - Haoran Sun; Hifza Mariam; Junnan She; Ming Chen; Dong Li; Chongya Jiang; Xia Yao; Iftikhar Ali; Yan Zhu; Weixing Cao; Tao Cheng (Remote Sensing of Environment, 2026)

Computational study on the hydrothermal cracking routes of N-cyclohexylnaphthalen-1-amine based on density functional theory - Shao-Xuan Zhong; Wei Li; Jia-Wei Qu; Ming-Lan Ge; Yuan-Liang Yang; Jian-Qiang Tao; Jing Wang (Fuel, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

A deep learning and generative modeling pipeline for mining and engineering alkaline-stsable xylanases - Ruohan Zhang; Yiyang Zhang; Zhonghao Deng; Pengtao Wang; Lingxi Fan; Feng Guo; Huiying Luo; Yuan Wang; Tao Tu; Bin Yao; Jian Tian; Huoqing Huang; et al. (Bioresource Technology, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Borborobacter xinjiangensis sp. nov., a moderately halophilic bacterium isolated from grapevine rootstock in Xinjiang, China - Xue Li; Yu Tao; Ming Li; Qingzhuang Zhang; Guohong Wu; Jinge Hu; Shijian Bai; Lei Su; Xin Li (Archives of Microbiology, 2026)

Gill remodelling in Hefang bream during hypoxia and reoxygenation: Histological and transcriptomic insights - Xinxin Yu; Minghui Xiao; Siyu Fan; Zhifeng Zhou; Zhong Tang; Ming Wen; Shengnan Li; Yuequn Wang; Min Tao; Shaojun Liu (Aquaculture, 2026)

Comparative study of the transient response and failure characteristics of lined tunnels under idealized and realistic plane P-wave seismic excitation - Hao Luo; Ming Tao; Hiroyuki Noda; Xibing Li; Chengqing Wu (Tunnelling and Underground Space Technology, 2026)

From waste to advanced materials: Converting fly ash into geopolymers for sustainable waste recycling - Shoujun Wang; Bin Li; Yue Zhao; Ming Xie; Yanyu Yang; Tingting Liu; Tao Zhou; Qihong Cen; Yong Liu; Zewei Liu (Journal of Environmental Chemical Engineering, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Integrating ecological networks and metagenomics to decipher core microbial drivers of organic acid metabolism during heaped fermentation of sauce-flavor Baijiu - Hong-Yan Zhang; Ting-Cai Huang; Li-Juan Chai; Wei Shi; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Research International, 2026)

An LAI-driven spectral critical curve based on the interference-mitigation chlorophyll index for nitrogen diagnosis in winter oilseed rape (Brassica napus L.) under contrasting mulching systems - Zijun Tang; Liang Cheng; Yannian Li; Zhiying Liu; Tao Sun; Fanghao Tao; Ming Jin; Xueyan Zhang; Fucang Zhang; Youzhen Xiang (Field Crops Research, 2026)

Numerical study on path dependence in transient unloading of rock masses under non-hydrostatic pressure - Gongliang Xiang; Ming Tao; Rui Zhao; Xibing Li; Wenzhuo Cao (Computers and Geotechnics, 2026)

Unlocking the carbon sequestration potential of agricultural soils: Stoichiometric control of mineral-associated organic carbon saturation - Xiaopeng Shi; Tao Feng; Jianjun Yang; Xulong Zhang; Ming Zhang; Feng Zhang; Xiaojing Zhang; Anming Yuan; Feng-Min Li (CATENA, 2026)

Estimation of Potato Plant Nitrogen Content Using Hyperspectral Indices and Machine Learning Models - Ming Jin; Juanli Ju; Siqi Li; Xiaochi Liu; Chen Li; Kang Zhu; Tao Sun; Zijun Tang; Youzhen Xiang; Zhijun Li; Fucang Zhang (Potato Research, 2026)

Soil macrofauna mucus bacterial community: Insights from cultured earthworms and snails - Jia-Jia Gu; Ming-Xin Li; Shuai-Fei Ye; Qiu-Yu Gan; Si-Si Chen; Cheng-Wei Tao; Jing Wen; Xin-Li An; Yu-Ling Jiang; Hong-Tao Wang (Soil Ecology Letters, 2026)

Field-deployable RspCas13d platform for rapid and extraction-free detection of giant panda- and canine-derived Canine Distemper virus - Qian Tao; Yuxiao Xing; Haidi Yang; Linhua Deng; Ming He; Yanxi Cheng; Qian Wang; Zhan Gao; Haohong Wan; Desheng Li; Shanshan Ling (Analytica Chimica Acta, 2026)

Revealing the anti-ferroptosis guanidine alkaloids from Buthus martensii Karsch via a NMR-guided isolation combined with in vitro, in silico, and network pharmacology - Wen-Kai Zhao; Tao-Li Hao; Ya-Zhou Kuang; Tong Sun; Hong-Bing Zhang; Yu-Ming Liu (Natural Product Research, 2026)

Optimized retrievals of aerosol optical properties from directional polarimetric camera using optimal linear mixture of basis aerosol models supported by the non-negative matrix factorization - Shikuan Jin; Yingying Ma; Deren Li; Wei Gong; Oleg Dubovik; Jin Hong; Zhenghai Liu; Cheng Chen; Zhongting Wang; Tao He; Yunduan Li; Boming Liu; et al. (Remote Sensing of Environment, 2026)

First report of mass mortality in post-metamorphosis Magallana gigas associated with OsHV-1 in China: epidemiological and genomic characterization - Bo-Wen Huang; Xiang Zhang; Tao Xu; Yi-Tao Zhang; Xiao-Ai Li; Lei Gao; Ning Kong; Ming-Kun Liu; Tao Yu; Hui-Gang Kang; Chong-Ming Wang; Chang-Ming Bai (Journal of Invertebrate Pathology, 2026)

A prefabricated Measurement While Drilling system for pneumatic anchor drills in mine - Haolin Wang; Longyun Wu; Liu Liu; Shaojun Li; Tao Wang; Ming Li; Junbo Zhou; Guofeng Liu; Jiyun Zhang (Journal of Applied Geophysics, 2026)

Performance and mechanism differences of thermal spallation in dry and water-saturated hard rocks - Yide Guo; Cheng Zhai; Xibing Li; Ming Tao; Linqi Huang; Yanwei Liu (International Journal of Rock Mechanics and Mining Sciences, 2026)

Cutting performance and fragmentation behavior of rock under confining stress: role of heterogeneity - Zheng Yang; Ming Tao; Tubing Yin; Yanliang Li (International Journal of Rock Mechanics and Mining Sciences, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

Synergistic microstructure–composition engineering in MOF-derived core–shell nano-reactors for enhanced peracetic acid activation toward sulfamethazine degradation - Shaoqun Tao; Mei Li; Yu Liu; Chenyu Zhao; Huiling Hao; Xin Guo; Wenxian Wei; Weichuan Qiao; Ming Zhang (Chemical Engineering Journal, 2026)

Fucosylated human milk oligosaccharides: A comprehensive review from structure and function to biomanufacturing and industrial perspectives - Mengli Li; Jiawei Yao; Ruoyu Jia; Mo Han; Ming Miao; Tao Zhang (Carbohydrate Polymers, 2026)

Concentration-dependent variation in carbon allocation and microbial assembly in chain elongation microbiota: Comparative effects of acetate, ethanol, and lactate - Ya-Ning Song; Li-Juan Chai; Ling Ao; Jun-Lan Mei; Yu-Long Li; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Bioresource Technology, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

Corrigendum to: “Benzo[a]pyrene exposure promotes RIP1-mediated necroptotic death of osteocytes and the JNK/IL-18 pathway activation via generation of reactive oxygen species” [Toxicology, 476, June 2022, 153244] - Tao Zhang; Yuchen Shen; Ruirong Zhu; Weiyan Shan; Yurong Li; Ming Yan; Yun Zhang (Toxicology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Dimefluthrin-induced multigenerational endocrine toxicity in zebrafish (Danio rerio) offspring via parental exposure - Wei-Guo Wang; Rui-Rui Li; Ming-Jun Yang; Jing-Ying Hu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Discovery and exploration of lignans from Dendrobiun chrysotoxum as new botanical insecticides against Acyrthosiphon pisum and Bursaphelenchus xylophilus - Wen-Yu Wang; Yue-Tong Zhu; Chuan-Le Guo; Bo-Tao Lu; Chun-Huan Li; Jin-Ming Gao; Meng Yang (Pesticide Biochemistry and Physiology, 2026)

Deciphering Qu-aroma in Nongxiangxing baijiu via a customized aroma base solution - Sheng-Bing Yang; Zhen-Ming Lu; Jia-Nan Hu; Ting-Yao Tu; Man-Si Niu; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; et al. (Food Research International, 2026)

Integrated transporter engineering and metabolic flux redistribution for efficient production of 3-fucosyllactose in Escherichia coli - Ruoyu Jia; Mengli Li; Mo Han; Juan Zhang; Ming Miao; Tao Zhang (Food Bioscience, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Revealing phenological vulnerabilities in wheat yield formation under climate warming: a process-based framework for adaptive breeding - Ming Li; Shizhao Li; Xiaoli Wu; Ling Wu; Miao Liu; Tao Xiong; Chaosu Li; Yonglu Tang (Agricultural and Forest Meteorology, 2026)

Fragmentation Performance and Mechanisms of Different Drilling Pattern in Multi-hole Blasting - Yuanquan Xu; Ming Tao; Zhixian Hong; Rui Zhao; Haibo Li; Xibing Li (Rock Mechanics and Rock Engineering, 2026)

UAV-based crop pest and disease monitoring: A review of multi-source sensing and intelligent methods - Jie Guo; Jin-Hai Li; Le Dong; Shun-Yu Wang; Guang-Yue Wu; Yu-Peng Zhang; Chang-Yong Tao; De-Hua Gao; Shu-Ming Yang; Yu-Tan Wang (Computers and Electronics in Agriculture, 2026)

IL-8-expressing recombinant Bacillus subtilis: A novel immunostimulant for improving production efficiency and disease resilience in Sebastes schlegelii aquaculture - Qing Yang; Hong-Yu Jiang; Ming-Tao Li; Bin-Tong Yang; Shu Li; Wei Cong; Yuan-Huan Kang (Aquaculture, 2026)

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Iron oxide-apatite and porphyry Cu–Au deposits controlled by pre-ore degassing, emplacement depths, and evaporite assimilation: A comparative study of the Nihe Fe and Shaxi Cu–Au deposits, Anhui, China - Yi Li; Ke-Zhang Qin; Le Wang; Guo-Xue Song; Tao-Fa Zhou; Yong-Jian Wang; Ming-Guo Zhai (Gondwana Research, 2026)

Exploring primate immune responses to SLA-I/II knockdown pig xenografts in humanized mice and rhesus monkeys - Ming-Hui Fang; Hao Feng; Kai Xu; Tang Hai; Song Chen; Ji-Long Ren; Wei-Gang Wang; Yuan-Tao Wang; Jun Zou; Fei Xu; Zi-Yue Wang; Yi-Wei Yao; et al. (Science China Life Sciences, 2026)

Warming inhibits the solubilization effect of organic acids on Fluvisols mineral P, partitioning to organic P - Liping He; Junyan Liu; Bo Lan; Li Gu; Kehong Wang; Duoyan Liao; Ming Wen; Bo Tong; Tao Tian; Yuhan Gu (Journal of Soils and Sediments, 2026)

Recent advances in the discovery, heterologous expression, protein engineering, and immobilization of cellobiose 2-epimerases - Sijia Yang; Mengli Li; Tao Zhang; Ming Miao (Trends in Food Science & Technology, 2026)

A potent TGF-β heterodimer orchestrates germ cell homeostasis in fish - Ming-Tao Wang; Chun Miao; Sheng Yang; Zhi Li; Meng-Di Zhu; Jie He; Miao Ding; Si-Wei Wu; Yang Zhang; Shun Li; Meng Lu; Peng Yu; et al. (Science Bulletin, 2026)

Avermectin disrupts blood-brain barrier integrity in zebrafish larvae via the Wnt/β-catenin signaling pathway - Wei-Guo Wang; Lin-Jing Du; Huan-Ou Ma; Wen-Ping Xu; Li-Ming Tao; Zhong Li; Jia-Gao Cheng; Li Zhao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Pennsylvanian (Bashkirian) microbial reefs from Guizhou Province, South China: Characteristics and insights into the middle Carboniferous microbial reef development - Guan-Ming Lai; Yong-Li Zhang; En-Pu Gong; Ning-Feng Du; Wen-Tao Huang; Deng-Hui Chen; Yu Li; De-Peng Li (Palaeoworld, 2026)

TomOmics: An integrative multi-omics platform for comparative and functional research in tomato - Yan Wang; Tailai Yang; Yuru Song; Qinqin Yang; Xiao Su; Hongwei Li; Yushan Li; Ming Zhou; Tao Lin (Molecular Plant, 2026)

Apparent resistivity evaluation method of slurry diffusion-solidification and grouting effect of water-bearing fractured rock mass - Hao Xu; Zhen-zhong Xing; Sheng-quan He; Lian-zhi Yang; Yi Zhu; Da-zhao Song; Yu Zhang; Jin-tao Dang; Qiang Liu; Li-ming Qiu; Ping Wang (Journal of Applied Geophysics, 2026)

Loss analysis and performance optimization of high-efficiency G-M type pulse tube cryocoolers operating at liquid helium temperatures - Ruize Li; Haoren Wang; Zhicai Zhang; Kaihao Zhang; Qinyu Zhao; Qingnan Zhang; Ming Wu; Bo Wang; Tao Jin; Zhihua Gan (International Journal of Refrigeration, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Hexavalent chromium induces death of porcine spermatogonial stem cells via promoting mitophagy and ferroptosis - Tianjiao Li; Rongnan Li; Zhucheng Wang; Ming Guo; Meimei Wang; Xin Li; Chang Liu; Wenxian Zeng; Tao Li (Environmental Toxicology and Pharmacology, 2026)

Coupled influence of Western Pacific moisture anomalies and mid-tropospheric humidity on October precipitation in Yunnan Province Southwest China - Wen-Jun Sun; Zhen-Peng Tao; Zi-Yang Zhang; Tian-Qing Lan; Taohui Li; Peng Zi; Jian Zhang; Yao Wu; Ming-Qiang Liang; Chao-Jun Chen; Yuan-Yuan Mu; Jun-Yun Li; et al. (Atmospheric Research, 2026)

Effects of hummock-hollow microtopography on CO2 and CH4 emissions from sedge peatlands in the Changbai Mountains, Northeast China - Xingli Li; Ming Wang; Shangqi Xu; Chris Freeman; Guodong Wang; Tao Zhang (Agricultural and Forest Meteorology, 2026)

Effects of parachute science on local research capacity 降落伞科学对当地研究能力的影响 - Li Yang; Tao Chen; Colin A. Chapman; Paul A. Garber; Yu Xuan Fan; Tien Ming Lee; Michael Huffman; Juan Carlos Serio Silva; Carlos Peres; Onja H. Razafindratsima; Lwin Ngwe; Peng Fei Fan (Conservation Biology, 2026)
Strengthening research capacity is essential to address the global biodiversity crisis. Yet, parachute science often undermines this goal, and its prevalence, costs, and benefits are unclear. We analyzed 13,502 publications on primate research that we extracted from Scopus (1960–2022) to evaluate the effects of parachute science on local research capacity across primate‐range countries. We categorized these publications as local (LRP), collaborative (CRP), or parachute science (PSRP) research publications and categorized countries where the research took place as low‐ to middle‐income countries or high‐ to upper‐middle‐income countries. We used generalized linear mixed‐effects models to assess how parachute science influenced local research capacity. For 69% of PSRPs, the research was conducted in 59 low‐ to middle‐income countries. For 20% of LRPs, research was led by people from these 59 countries. The disparity in LRPs among country groups was large. Local research publications in high‐ to upper‐middle‐income countries were at least 3.6 times higher than those in low‐ to middle‐income countries. Before 2013, parachute science contributed to an increase in LRPs; this trend reversed after 2013, mainly resulting in a decline in LRPs across all countries and both income categories. Strengthening the capacity to share research in low‐ to middle‐income countries is urgent if international conservation commitments are to be met. We recommend establishing true collaborative and interdisciplinary research teams, expanding local research opportunities, and supporting long‐term research projects as key strategies for sustainable research capacity strengthening in low‐income countries.

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Iceberg detection from global open ocean sentinel-1 wave mode SAR data with YOLO deep learning - Tao Xie; Chen Wang; Xiao-Ming Li; Huimin Li; Gaojing Fan; Alexis Mouche; Bertrand Chapron (Remote Sensing of Environment, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

NF8: A miniature pentameric coiled-coil fusion tag for enhanced recombinant protein expression - Junshi Zhou; La Xiang; Huan Niu; Yufeng Cao; Shizhong Li; Huaiyi Yang; Yong Tao; Jian-Ming Jin; Chaoning Liang; Shuang-Yan Tang (Chemical Engineering Journal, 2026)

Programmable amylose architectures via α-glucan phosphorylase coupling: From process variables to structure–property map - Wei Gao; Mengli Li; Ming Miao; Tao Zhang (Carbohydrate Polymers, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Characterization of a new isolate of tomato zonate spot virus from Vaccinium uliginosum L. in China - Yueyan Yin; Tao Lin; Ru Dong; Zhijiao He; Jing Zhong; Liling Zhao; Jiawei He; Ming Ding; Tingting Li (Journal of Plant Pathology, 2026)

Effects of Dietary Lipid Levels on Growth Performance and Transport Stress Tolerance in Channel Catfish (Ictalurus punctatus) - Tao Teng; Dehong Zhang; Jianhua Ming; Hualiang Liang; Li Cai; Tingting Li; Xiufang Ren; Lu Zhang; Haifeng Mi (Fishes, 2026)
This study aimed to investigate the effects of dietary lipid levels on growth performance and transport stress resistance in large-sized channel catfish (Ictalurus punctatus). Four experimental diets were formulated with fat levels of 7.5% (control), 10.0%, 12.5%, and 15.0%, using soybean oil as the lipid source. Each diet was assigned to four replicate groups in a 110-day feeding trial, with fish averaging 600.61 ± 1.33 g at the start. Results showed that increasing dietary fat enhanced weight gain rate (WGR) and specific growth rate (SGR), with the 15.0% fat group achieving the best growth performance and the lowest feed conversion ratio (FCR), significantly lower than the control (p

The catalytic subunit of cAMP-dependent protein kinase in Taenia solium cysticerci (TsPKA-c): A promising molecular target for the development of novel anti-cysticercosis therapeutics - Li-Qun Wang; Guang-Xue Liu; Pan-Hong Liang; Li Li; Tao-Shan Li; Ai-Ming Guo; Tharheer Oluwashola Amuda; Ke-Ke Wu; Yi-Xuan Wu; Hong Yin; Hong-Bin Yan; Xue-Nong Luo (Veterinary Parasitology, 2026)

Prevalence and genomic characterization of pathogenic blaNDM-positive Escherichia coli from retail meats: The first large-scale study in 22 cities of China - Mei-Jun Chu; Ming Zou; Han Wang; Junjie Wang; Zhiyuan You; Yan Li; Bao-Tao Liu (Food Microbiology, 2026)

ZIF-67 derived NiCo-LDH nanoflowers in-situ Co-inherited grown on ZnO@CoCu for high performance asymmetric supercapacitors - Wenxin Chen; Tao Tang; Chaoran Lin; Hexu Wang; Dancheng Yang; Ziyi Qiao; Ming Li; Aimiao Qin; Jianfeng Wen; Guanghui Hu; Li Jiang (Chemical Engineering Journal, 2026)

Ultrasensitive and label-free detection of piR-54265 biomarker by solution-gated graphene transistors with poly-adenine DNA assembled probe for accurate diagnosis of colorectal cancer - Tingting Yu; Peng Song; Ruixue Wang; Ziwen Chen; Liang Zhao; Ming Wang; Jianying Wang; Tao Mei; Xianbao Wang; Jinhua Li (Chemical Engineering Journal, 2026)

Cyflumetofen induces hepatic steatosis and disrupts lipid metabolism in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Da-Wei Yan; Lan Xu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

Subcellular Structures in Native Hippocampal Synapses Revealed by Cryo-electron Tomography - Chong-Li Tian; Lei Qi; Zhen-Hang Lu; Shuo Liu; Min-Ling Gu; Wen-Lan Huang; Yi-Tong Yan; Yun-Tao Liu; Jing Wu; Peiyi Wang; Z. Hong Zhou; Guo-Qiang Bi; et al. (Neuroscience Bulletin, 2026)

Simultaneous remediation of heavy metals in mining soil using nZVI-supported attapulgite - Jun Ren; Caili Tong; Hanru Ren; Ming Gao; Gui Ma; Yunmeng Li; Rui Zhu; Xuri Mu; Chun Yang; Ling Tao (Environmental Geochemistry and Health, 2026)

Effects of hummock–hollow microtopography on soil microbial communities and their links to soil carbon cycling in a sedge peatland of the Changbai mountains - Biyu Shi; Ming Wang; Guodong Wang; Xingli Li; Tao Zhang (Applied Soil Ecology, 2026)

Global Patterns and Drivers of Recent Decoupling Between Extratropical Spring Phenology and Temperature - Ziyu Lu; Ming Shao; Jiayan Li; Jingyuan Lin; Peiyuan Tao; Mengyu Li; Siqi Zhang; Peng Yao; Yang Fu (Global Change Biology, 2026)
While spring phenology has been widely studied, the magnitude and drivers of its decoupling from thermal cues across extratropical biomes remain poorly understood. Using satellite data from 1982 to 2021, we show that the onset of vegetation green‐up (GSOS) generally lags the onset of the thermal growing season (TSOS). This mismatch (ΔSOS) has increased by 1.51 days per decade ( p 15 days), warming‐driven advances in TSOS are increasingly decoupled from GSOS, as declining precipitation and enhanced evaporative demand intensify moisture limitation and delay green‐up; in temperate forests (both coniferous and broadleaf), warming together with enhanced shortwave radiation promotes faster GSOS advancement relative to TSOS, thereby dampening the mismatch. These contrasting pathways reveal an accelerating yet heterogeneous phenology–temperature decoupling, with far‐reaching consequences for ecosystem synchrony, seasonal carbon uptake, and land–climate feedbacks. Our results underscore the need to incorporate non‐thermal drivers and biome‐specific controls into phenological and Earth system models to better constrain future climate–biosphere interactions.

The Role of Atlantic Multidecadal Oscillation in Decadal Summer Temperature Variability Over the Tibetan Plateau in Observations and Pacemaker Simulations - Yanfeng He; Minhua Qin; Chuntao Yu; Huiting Feng; Hongwei Chen; Ming Li; Tao Wang; Min Wan; Shanlei Sun; Wenjian Hua (International Journal of Climatology, 2026)
Previous studies have suggested that internal oceanic modes such as the Interdecadal Pacific Oscillation (IPO) and Atlantic Multidecadal Oscillation (AMO) have significant effects on the decadal temperature variability over the Tibetan Plateau (TP). However, assessments of decadal variability are very sensitive to the length of study periods. Thus, the dominant factors regulating the decadal temperature variations over the TP and the associated mechanisms have not been clearly identified. This study utilised long‐term temperature observations, global reanalysis and climate model simulations to examine the decadal variations and the underlying mechanisms of surface air temperature (SAT) over the TP during boreal summer from 1901 to 2020. Results show that there exist decadal variations in summer TP SAT, with warm periods during 1929–1960 and 1999–2020 and cold periods during 1901–1928 and 1961–1998. It has also been found that the decadal changes in summer TP SAT are closely associated with the AMO. In contrast, TP SAT has a weak relationship with the IPO during 1901–2020. North Atlantic pacemaker simulations further show a zonal wave train pattern propagating from the North Atlantic to East Asia, which triggers anomalous anticyclonic circulations over the northern TP and Lake Baikal. The regional anticyclonic circulation anomalies over the TP not only weaken the subtropical westerly jet stream but also facilitate the water vapour transport into the TP and further cause local warming over the TP. Our findings elucidate the role of internal climate variability in shaping the decadal variability of summer TP SAT and also help reduce uncertainties in future projections of TP SAT changes.

Mechanistic Insights into the Differential Toxicity and Antagonistic Interactions of the Rare Earth Elements Cerium and Yttrium Toward Rice Roots - Yingyi Meng; Wanshu Li; Di Ming; Xiaoyan Bai; Lingqing Wang; Tao Liang (Biological Trace Element Research, 2026)

Unveiling the adsorptive/catalytic roles of micro-carbon sphere materials in antibiotic removal: Current status and perspectives - Ning Wang; Wang-mi Chen; Qi Zhou; Yu Dong; Ming-xiao Li; Bei-dou Xi; Jia-qi Hou; Zhen-tao Cui (Water Research, 2026)

Enhancing climate resilience of global dryland maize to cope with future 50-year climate warming - Jing Wang; Bao-Zhong Wang; Fei Mo; Yinglong Chen; Mohammad Ashraf; Yang Wang; Jian-Ming Li; Hai-Xia Duan; Yajie Song; Levis Kavagi; Hong-Yan Tao; You-Cai Xiong (Global Environmental Change, 2026)

Cereal-legume intercropping stabilizes yield and economic advantages under variable rainfall in semiarid rainfed environment - Wei Wang; Bao-Zhong Wang; Wei Zhang; Meng-Ying Li; Jian-Ming Li; Sheng-Jun Ji; Muhammad Abrar; Muhammad Maqsood Ur Rehman; Wasim Khan; Hong-Yan Tao; Mohamed S. Sheteiwy; Wen-Ying Wang; et al. (European Journal of Agronomy, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Two-dimensional Ru single-atom arrays anchored on LaAlO3 perovskite enable highly active and stable dry reforming of methane - Xuyingnan Tao; Pengcheng Yu; Haoran Yu; Feiyang Yu; Tingting Zhao; Ming Li; Xiaolong Zhang; Haiqian Wang (Chemical Engineering Journal, 2026)

6PPD-Q degradation by self-powered bio-electro-Fenton and response of functional microbial communities - Gaolei Liu; Rongrong Mao; Ming Yan; Jinzheng Liu; Weitao Liu; Tao Hua; Fengxiang Li (Chemical Engineering Journal, 2026)

Sequential drug-releasing electroactive wound dressing accelerates healing of diabetic infected wounds through microenvironmental remodeling - Dapeng Cui; Ziyuan Yang; Yupeng Zhang; Xiaopeng Suo; Ming Cheng; Shuang Fan; Cheng Yang; RuiXia Yu; Tao Wang; Lei Li; Jiaxin Cui; Zhongdi Liu; et al. (Chemical Engineering Journal, 2026)

Cyflumetofen disrupts the blood-brain barrier and induces neurotoxicity in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

The composite applications of Power Domain Deconvolution and Synchrosqueezed Generalized S Transform in the South China Sea - Xiu-ming Li; Hai-tao Yan; Nan-ke Wu; Chang-cheng Xiang (Applied Geophysics, 2026)

Tailoring the Si/Al ratio of Fe-SSZ-13 catalysts for enhanced catalytic N2O decomposition - Shujun Ming; Zhen Zhu; Lei Pang; Sheng Su; Xuannan Zhou; Feifei Xie; Shiya Pang; Yarong Fang; Tao Li (Journal of Environmental Chemical Engineering, 2026)

Differential regulation of root iron plaque formation in a mangrove species, Kandelia obovata by biodegradable and conventional nanoplastics: Evidence from interfacial interactions, microbial communities, and redox conditions - Ming Li; Jie Gao; Nora Fung-Yee Tam; Haichao Zhou; Min Pan; Fred Wang-Fat Lee; Steven Jing-Liang Xu; Jian Liu; Kaixuan Deng; Peng Zheng; Cheng Ye; Xinran Ke; et al. (Environmental Pollution, 2026)

Creep of water-bearing soft rock and its influence on long-term rock mass stability - Zhao-Qiang Zheng; Li Zhuo; Jian-Liang Pei; Ming-Li Xiao; Huai-Zhong Liu; Hong-Qiang Xie; Tao Luo (Engineering Geology, 2026)

Engineering the cathode: Key to unlocking the potential of potassium-ion batteries - Yu Dong; Ning Wang; Wang-mi Chen; Qi Zhou; Ming-xiao Li; Zhen-tao Cui; Jia-qi Hou; Wen-lin Ruan; Bei-dou Xi (Chemical Engineering Journal, 2026)

Effective elimination of malachite green from solutions by functionalized hydrochar derived from co-hydrothermal carbonization of bamboo and polyvinyl chloride with ammonium persulfate assistance - Jia-Ming Zhao; Qian Zhang; Ying-Tao Su; Xiao-Man Huang; Bing Li (Chemical Engineering Journal, 2026)

Prediction and Safety Control of Blast-Induced Vibrations in Shallow-Buried Soft Rock Tunnels - Haixian Huang; Qiyue Li; Li Li; Xibing Li; Ming Tao (Rock Mechanics and Rock Engineering, 2026)

Amino-modified gangue-derived NaX zeolite for enhanced stabilization of lead and cadmium in contaminated soils: synthesis, performance, and leaching stability - Weiwei Zhu; Jingyi Xiong; Zhuoxi Huangfu; Jiang Yu; Pengxinyue Hang; Cheng Han; Ming Chen; Bin Li; Tao Gao; Junwei Yang; Yao Du (Environmental Geochemistry and Health, 2026)

Characterization and production optimization of genistein by the novel endophytic fungus Aspergillus sydowii J11 isolated from pigeon pea (Cajanus cajan) and its antibacterial and antioxidant properties - Bin-bin Li; Xuexia Gao; Min Lv; Wen-juan Ning; Jing-tao Liang; Xin-yu Fan; Xin-ming Lv; Jin-feng Song; Xiao-han Yuan; Cheng-bo Gu (Biotechnology Letters, 2026)

Exploring 3D Seismic Acquisition, Imaging, and Data Quality: A Systematic and Bibliometric Review - Frank Ofowena; Akhmal Sidek; Ming-tao Nie; Li-xin Zhai; Jamal Ahmad (Applied Geophysics, 2026)

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

Gonadal temperature-sensitive gene identification in gynogenetic gibel carp (Carassius gibelio) with temperature-dependent sex determination - Wen-Xuan Du; Zhi Li; Tao Wang; Miao Ding; Ming-Tao Wang; Chun Miao; Xiao-Juan Zhang; Yang Wang; Zhong-Wei Wang; Li Zhou; Jian-Fang Gui; Xi-Yin Li (Aquaculture, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Mechanistic insights into the enhancement of azithromycin biodegradation by extracellular polymeric substances: Roles of metabolic activity, electron transfer, and reactive oxygen species - Jian-Gang Zhou; Ming-Hong Wei; Shi-Jie Wang; Li Chen; Muhammad Wajid Ullah; Hong-Tao Liu; Su Sun (Journal of Hazardous Materials, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

amh alleles on XY sex chromosomes regulate male differentiation in amphidiploid Carassius auratus - Chun Miao; Meng Lu; Miao Ding; Ming-Tao Wang; Zhi Li; Tian-Zi Yao; Zhi-Xuan Zhu; Wen-Xuan Du; Jun-Sheng Niu; Xiao-Juan Zhang; Shun Li; Peng Yu; et al. (Science China Life Sciences, 2026)

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Chi-miR-146a promotes the propagation of Neospora caninum by targeting the TGF-β1/SMAD2 pathway - Jin-Ming Chen; Jing-Yu Li; Jia-Yi Jin; Xiao-Qi Bao; De-Liang Tao; Xiao-Yun Zhao; Jun-Ke Song; Xin Yang; Ying-Ying Fan; Guang-Hui Zhao (Veterinary Parasitology, 2025)

Multiscale Elucidation of kerogen heterogeneity in Lucaogou Formation based on experiment and simulation: Structural Determinants of reactivity and stability for shale oil conversion - Youjie Li; Huifei Tao; Zhuanhong Lu; Qian Wang; Ming Yan; Zaibo Xie; Zhongping Li (Fuel, 2025)

Corrigendum to “Identification and in vitro anti-inflammatory activity of different forms of phenolic compounds in Camellia oleifera oil” [Food Chem. 344 (2021) 128660] - Tao Zhang; Fangcheng Qiu; Li Chen; Ruijie Liu; Ming Chang; Xingguo Wang (Food Chemistry, 2025)

Fabrication and structure–function relationship of PLA/PBAT-based biodegradable food-grade films - Liping Wang; Dexiang Li; Lei Ye; Chaohui Zhi; Tao Zhang; Zhengyu Jin; Ming Miao (Food Bioscience, 2025)

Flux measurements of NOx, O3 and Ox: Emission characteristics, inventory validation and titration effects - Xiaoxiao Zhang; Bin Yuan; Yibo Huangfu; Huizhi Liu; Thomas Karl; Ming Chang; Shiyi Chen; Tao Song; Jintai Lin; Guannan Geng; Hongjuan Li; Eran Tas (Environmental Pollution, 2025)

Estimation of Chlorophyll Content in Potato Leaves Based on UAV Multi-Spectral and Thermal Infrared Images - Ming Jin; Juanli Ju; Siqi Li; Xiaochi Liu; Xiangyang Huang; Tao Sun; Zijun Tang; Youzhen Xiang; Zhijun Li; Fucang Zhang (Potato Research, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Serum cortisol and AdipoR2 rs12342 were involved in the correlation between stress and serum cholesterol in a gender-specific manner - Yi Lin Shen; Qi Wei Guo; Xue Cheng Li; Ke Xin Jia; Jun Yi Liu; Yan Zhi Yi; Jun Tao Ren; Jia Jing Cai; Guo Ming Su; Jia Lin; Ding Zhi Fang (Metabolic Brain Disease, 2025)

Exploring the main and interactive effects of urban morphology on land surface temperature across different functional zones: A local geoshapley analysis based on XAI - Jin-Tao Yang; Xing-Wen Zhou; Xu Chen; Xiong Yao; Mao Li; Ming-Hui Yin; Fei Dong; Shi-Hong Yan; Jia-Liang Zhao (Sustainable Cities and Society, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Structural characteristics and community formation mechanisms in aquatic plant communities during the near-natural restoration of urban rivers - Yijia Li; Ran Tao; Jie Zhang; Jiafei Zhang; Xiaomeng Zhang; Yunv Dai; Yiping Tai; Yang Yang; Ming Li; Qianhong Xuan; Wenling Zhu; Xinmin Zhou; et al. (Landscape and Urban Planning, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Blast-induced fracture mechanisms and fragmentation characteristics of brittle materials under anisotropic stress fields - Yuanquan Xu; Ming Tao; Rui Zhao; Lei Huang; Haibo Li (International Journal of Rock Mechanics and Mining Sciences, 2025)

Structure and functionality of micronized maize starch differing in amylose content - Liping Wang; Dexiang Li; Lei Ye; Chaohui Zhi; Tao Zhang; Ming Miao (Food Chemistry, 2025)

A novel thermophilic α-glucan phosphorylase enables molecular weight-tunable amylose biosynthesis from cellobiose via a dual-enzyme cascade system - Wei Gao; Ru Yang; Mengli Li; Ming Miao; Tao Zhang (Food Bioscience, 2025)

Multi-omics and random forest reveal lipid metabolism disruption and biomarkers in grass carp (Ctenopharyngodon idellus) exposed to 2-methylisoborneol - Huan Han; Jun-Ming Zhang; Kang Li; Justice Frimpong Amankwah; Xiang-Biao Zeng; Zi-Qian Shen; Xi-Chen Jin; Tao-Ying Chen; Jing-Wei Liu; Li-Ping Liu (Environmental Research, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Efficient de novo synthesis of 3-fucosyllactose in Escherichia coli via enzyme engineering and pathway refinement - Ruoyu Jia; Mengli Li; Ming Miao; Tao Zhang (Bioresource Technology, 2025)

Experimental Investigation of Rock Deformation and Energy Conversion Under Gradient Stress Conditions - Ming Tao; Xingyu Wu; Rui Zhao; Muhammad Burhan Memon; Xibing Li (Rock Mechanics and Rock Engineering, 2025)

ZWINT down-regulated by miR-495-3p inhibited lung metastasis of breast cancer by blocking p38 MAPK signaling pathway activation - Ming-tao Shao; Wei-wen Li; Yong Li; Ping Chen; Shuai-shuai Yu; Wen-jie Lu; Chun-mei Chen; Yan Dong; Yi-wen Zhang; Qun-chen Zhang (Human Cell, 2025)
Breast cancer metastasis is the primary cause of patient mortality, yet effective therapeutic targets remain limited. Building on our prior identification of ZWINT as a prognostic marker linked to metastasis, this study defines its critical functional role and regulatory mechanism. Multi-omics analysis revealed a strong association between ZWINT expression and metastatic processes across breast cancer subtypes. Functionally, ZWINT knockdown significantly inhibited breast cancer cell migration and invasion in vitro and dramatically reduced lung metastasis in vivo. Mechanistically, we discovered that miR-495-3p directly targets and suppresses ZWINT expression, and this miR-495-3p/ZWINT axis acts through inhibiting p38 MAPK pathway activation to suppress metastatic progression in vitro. Our findings demonstrate that ZWINT drives breast cancer metastasis and is negatively regulated by miR-495-3p. The newly identified miR-495-3p/ZWINT/p38 MAPK axis may provide a promising therapeutic target for suppressing breast cancer progression.

Modeling of carbon sink for concrete structures: From hydration kinetics to climate-driven carbonation - Ye Tian; Jia-Cheng Xu; Guo-Yi Zhang; Zu-Shi Tian; Bei Li; Ruo-Yi Zhao; Qiang Zeng; Bo-Tao Huang; Dong-Ming Yan (Sustainable Chemistry and Pharmacy, 2025)

Sodium alginate as a stabilizer for anthocyanins in Dendrobium officinale: Insights from experimental approach and molecular dynamics - Wenyang Tao; Chenchen Yang; Mengzhu Wang; Jingrui Li; Wanyi Zhou; Ming Li; Jianrong Xing; Yuping Zhao; Ying Yang (Food Chemistry, 2025)

Comparison of the host-pathogen interactions between Pseudomonas plecoglossicida and Nocardia seriolea in a cell line derived from head kidney of yellow large croaker - Li-Yun Jin; Shu-Ya Li; Fei Yin; Zhen Tao; Xiao Xie; Su-Ming Zhou (Fish & Shellfish Immunology, 2025)

A ratiometric fluorescence probe based on curcumin and supramolecular deep eutectic solvent for in vivo imaging cerebral pH - Wan-Chun Luo; Jin-Tao Zhang; Li-Na Bao; Lin-Jiao Yang; Zi-Ke Yang; Ming Jiang; Xu Yu; Li Xu (Chemical Engineering Journal, 2025)

Moisture-adaptive cellulose/MXene aerogels for synergistic moisture and triboelectric energy harvesting - Jiwei Zhang; Xinran Zhou; Mengjie Wu; Liming Zhu; Zechang Ming; Weikang Li; Yong Xia; Hao Liu; Zijie Zhou; Tao Zhang; Minghui Fan; Jianyong Yu; et al. (Chemical Engineering Journal, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Avermectin disrupted hematopoietic development and lipid metabolism in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Wen-Ping Xu; Li-Ming Tao; Xu-Sheng Shao; Zhong Li; Li Zhao; Yang Zhang (Journal of Hazardous Materials, 2025)

Comparative metagenomic analyses of viral genomic diversity and ecosystem functions in extremely acidic copper mine tailings - Pei-Zhe Ye; Qiang Yang; Chu-Yi Zhang; Tao-Tao Yang; Sheng-Fang Jiang; Rui Lan; Shao-Ming Gao; Li-Nan Huang (Journal of Hazardous Materials, 2025)

Petrological and thermodynamic constraints on carbonate stability in altered oceanic crust subducted to subarc depths: Insights from carbonate-bearing eclogites in the Western Alps - Zeng-Li Guo; Jin-Xue Du; Li-Fei Zhang; Thomas Bader; Ren-Biao Tao; Ze-Ming Zhang; Kurt Bucher; Ting-Nan Gong; Jin-Hong Yu (Geochimica et Cosmochimica Acta, 2025)

Soil mesofauna bacterial diversity: Insights from cultured collembolans, enchytraeids, and mites species - Bo-Wen Liu; Jing Wen; Shuai-Fei Ye; Jia-Jia Gu; Ming-Xin Li; Xiao-Bo Xiong; Zong-Zheng Liang; Hong-Tao Wang (Food Webs, 2025)

Investigation on quality discrepancies of Soy Sauce Aroma Baijiu: Flavor chemical characteristics in single-source and cross-source samples - Chen Li; Xiao-Juan Zhang; Shi-Yi Wang; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Bo Yang; Cai-Hong Shen; Zheng-Hong Xu (Food Control, 2025)

Estimation of Potato Leaf Area Index and Aboveground Biomass Based on a New Texture Index Constructed from Unmanned Aerial Vehicles Multispectral Images - Siqi Li; Youzhen Xiang; Ming Jin; Zijun Tang; Tao Sun; Xiaochi Liu; Xiangyang Huang; Zhijun Li; Fucang Zhang (Journal of Soil Science and Plant Nutrition, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Annual growth bands in the late Carboniferous reef-building colonial rugose coral Ivanovia and their environmental significance - Yong-Li Zhang; Wen-Tao Huang; En-Pu Gong; Guan-Ming Lai; Mark A. Wilson; Jun-Jie Wang; Ning-Feng Du; De-Peng Li (Palaeoworld, 2025)

Olfactory GnRH3 crypt sensory neurons transduce sex pheromone signals to induce male courtship behavior in zebrafish - Xuefan Cui; Lu Chen; Binbin Tao; Xiya Zhang; Yanlong Song; Ji Chen; Ming Duan; Weiwei Li; Kuangxin Chen; Yang Pei; Xuerui Hu; Ke Feng; et al. (Science China Life Sciences, 2025)

Methodology for oil film identification and feature extraction based on remote sensing data acquisition experiment - Ying Li; Tao Gou; Ming Xie; Shuang Dong (Marine Geodesy, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Formation pathways, migration characteristics, and inhibition mechanism of polychlorinated dibenzo-p-dioxins and dibenzofurans in hazardous waste incinerators: A comprehensive pilot-scale study - Fengyu He; Lei Yang; Dehua Liang; Ming Li; Jiawei Yan; Zhonghao Guan; Yang Xu; Fei Wang; Lang Tao; Zuhang Wu; Guojun Lv; Jianhua Yan (Journal of Hazardous Materials, 2025)

Avermectin induces photoreceptor functional impairment and color vision deficits in zebrafish (Danio rerio) - Wei-Guo Wang; Ming-Jun Yang; Zhu-Bo Sheng; Li-Ming Tao; Wen-Ping Xu; Yang Zhang (Journal of Hazardous Materials, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Cessation of manure application diminishes the dissemination potential of antibiotic resistance genes by altering bacterial interaction patterns in soil–lettuce systems - Ruochen Li; Xin Pei; Ming Zhang; Xuhui Deng; Chengyuan Tao; Jiabao Wang; Xueli Chen; Nicholas Clarke; Lidia Sas-Paszt; Zongzhuan Shen; Rong Li; Qirong Shen (Applied Soil Ecology, 2025)

Prediction of red tide outbreaks using time-series hyperspectral observations: implications on the optimal prediction model and spectral index - Ming Xie; Ying Li; Zhichen Liu; Tao Gou (Acta Oceanologica Sinica, 2025)

Endogenous storage proteins influence Rice flavor: Insights from protein-flavor correlations and predictive modeling - Mengdi Chen; Ming Zhang; Dong Wang; Shunqian Xu; Tao Chen; Ting Li; Xinxia Zhang; Li Wang (Food Chemistry, 2025)

Time series comparative genomics analysis reveals the adaptive evolution of caproic acid-producing bacteria to the long-term liquor brewing environment - Gan-Lin Li; Jun-Lan Mei; Li-Juan Chai; Xiao-Zhong Zhong; Ya-Ning Song; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Temporal and spatial differentiation in the landslide sediment transfer potential in Wenchuan earthquake-impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Jiangang Chen; Tao Yang; Lingfeng Gong; Qingyun Shi; Xianzheng Zhang; Ning Li; Mingwei Li (Landslides, 2025)

Dose-dependent inflammatory and neurotoxic effects of polypropylene microplastics in Nile tilapia evidenced by internal extractive electrospray ionization high-resolution mass spectrometry metabolomics - Xiaokang Wu; Susu Pan; Ming Li; Jiaxin Dong; Yining Wang; Chenni Huang; Tao Qiu; Yu Gu; Dapeng Liang (Environmental Chemistry Letters, 2025)

Effects of Temperature and Size on Secretion and Gene Expression of Digestive Hormones in Steelhead Trout (Oncorhynchus mykiss) - Rongxin Liu; Xiaoqun Chen; Yangen Zhou; Jinxiao Tan; Ming Huang; Tao Xu; Li Li; Yunwei Dong; Qinfeng Gao; Shuanglin Dong (Journal of Ocean University of China, 2025)

Construction and evaluation of recombinant rabies virus encoding three copies codon-optimized G genes as inactivated rabies vaccine in dogs and cats - Ying Wu; Haoqi Li; Zongmei Wang; Tao Pei; Qinghua Shang; Jianqing Zhao; Ming Zhou; Zhen F. Fu; Chengguang Zhang; Ling Zhao (Veterinary Microbiology, 2025)

Cereal-legume intercropping stimulates straw decomposition and promotes soil organic carbon stability - Wei Wang; Meng-Ying Li; Qing-Hui Wen; Yue Ma; Zhi-Ming Zhang; Muhammad Maqsood Ur Rehman; Fei Mo; Hong-Yan Tao; Bao-Luo Ma; Joann K. Whalen; You-Cai Xiong (Science China Life Sciences, 2025)

Experimental analysis on the optimal spectral index for the risk assessment of red tide occurrence - Ming Xie; Mian Qin; Ying Li; Zhichen Liu; Tao Gou (Journal of Oceanology and Limnology, 2025)

Risk prediction of catastrophic debris flows against the background of material changes and human engineering activity in the Wenchuan earthquake disturbance area - Jiang Xiong; Huayong Chen; Chuan Tang; Wanyu Zhao; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Jiangang Chen (Bulletin of Engineering Geology and the Environment, 2025)

Expectations for employing Escherichia coli Nissle 1917 in food science and nutrition - Miaomiao Hu; Tao Zhang; Ming Miao; Kewen Li; Qingmin Luan; Guilian Sun (Critical Reviews in Food Science and Nutrition, 2025)

Mechanism of hypoxia tolerance improvement in hybrid fish Hefang bream - Ming Wen; Chunchun Zhu; Yuhua Tang; Hong Zhang; Zheng Liu; Siyu Wang; Min Tao; Li Hu; Wenting Rao; Shengnan Li; Dingbing Gong; Shi Wang; et al. (Aquaculture, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

Chemically activating biomass into hierarchically porous carbon as an efficient sulfur host for high-performance room temperature Na-S batteries - Jiawang Liu; Heng Zhang; Baojian Xie; Junquan Cheng; Tao Song; Youcun Bai; Ruguang Ma; Chang Ming Li (Chemical Engineering Journal, 2025)

Geomorphometric assessment of spatial transfer potential of landslides sediment in seismically impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Chenxiao Tang; Lingfeng Gong; Ming Chen; Xianzheng Zhang; Tao Yang; Ning Li; Qingyun Shi; Mingwei Li (Natural Hazards, 2025)

Experimental study on the supernormal mechanical properties and antiknock properties of NPR steel - Yong Li; Wei Ming; Zhigang Tao; Jing Zheng; Manchao He (Tunnelling and Underground Space Technology, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Multi-level metabolic engineering of 6ʹ-sialyllactose in Escherichia coli - Chenchen Li; Mengli Li; Mo Han; Ming Miao; Tao Zhang (Food Bioscience, 2025)

Two-stage anomaly detection for imbalanced bridge data by attention mechanism optimisation and small sample augmentation - Chun-Xu Qu; Yun-Tao Yang; Hong-Ming Zhang; Ting-Hua Yi; Hong-Nan Li (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Local coordination configuration of Ni and Co in MgAl2O4 spinel structure and the performance of NiCo/MgO-Al2O3 catalyst for dry reforming of methane - Xuyingnan Tao; Feiyang Yu; Pengcheng Yu; Haoran Yu; Tingting Zhao; Ming Li; Haiqian Wang (Chemical Engineering Journal, 2025)

Highly accurate deformation adaptive pressure sensor integrated with programmatically fabricated strain localizing yarn - Yiming Ke; Weibing Zhong; Xiaojuan Ming; Kaiyue Cui; Shifan Song; Kangyu Jia; Mufang Li; Yi Xiong; Tao Zhao; Dong Wang (Chemical Engineering Journal, 2025)

Review on bioproduction of sialylated human milk oligosaccharides: Synthesis methods, physiologic functions, and applications - Chenchen Li; Zhu Liu; Mengli Li; Ming Miao; Tao Zhang (Carbohydrate Polymers, 2025)

A robust index was extracted to assess the prolonged changes in debris flow activity after a high magnitude earthquake - Jiang Xiong; Huayong Chen; Chuan Tang; Chenxiao Tang; Jiangang Chen; Tao Yang; Lingfeng Gong; Ming Chen; Qingyun Shi; Ning Li (CATENA, 2025)

Research on Support Control of New Materials and Structures for Deep Buried Complex Soft Rock Tunnel with Large Deformation - Yong Li; Jing Zheng; Chuang Xu; Manchao He; Fengnian Wang; Zhigang Tao; Wei Ming (Rock Mechanics and Rock Engineering, 2025)

Linking microbial nutrient limitation and community composition to nitrogen mineralization in bamboo forest soil with phosphorus addition - Tong-Tao Hu; Dong Bu; Yang Zhang; Fang-Chao Wang; Jian-Jun Li; Kui-Ling Zu; Ming-Hui Meng; Chao Liang; Xiang-Min Fang (Soil Ecology Letters, 2025)

Low-Frequency Sweep Design—A Case Study in Middle East Desert Environments - Yong-fei Qi; Zhou-hong Wei; Ming-tao Nie; Guo-fa Li; Tao Wang; Hai Ling; Sheng-kui Cong; Xin-yang Chen; Chang-ping Duan; Yang Liu (Applied Geophysics, 2025)

CDC42 enhances phagocytic activity and exhibits antimicrobial functions through the recruitment of IQGAP1 in Apostichopus japonicus - Xin Li; Wenjun Tao; Ming Guo; Chenghua Li (Aquaculture, 2025)

Response of soil organic carbon stocks and soil microbial biomass carbon to natural grassland conversion: A global meta-analysis - Yijun Cai; Yuwen Yang; Jinlin Jiang; Tao Long; Xueyuan Gu; Yang Guo; Ming Li; Yufeng Xie (Science of The Total Environment, 2025)

The regulatory mechanism controlling nitrification inhibitors-induced mitigation of nitrification and NO3−-N leaching in alkaline purple soil - Fabo Liu; Prakash Lakshmanan; Wenxin Zou; Ming Lang; Zhao Lei Li; Fen Zhang; Tao Liang; Jing Chen; Yan Wang; Xiaozhong Wang; Xinping Chen (Journal of Environmental Management, 2025)

Responses of soil respiration and its temperature sensitivity to nitrogen and phosphorus depositions in a riparian zone - LiPing He; XuLi Huang; KaiTao Jia; KeHong Wang; Bo Lan; Li Gu; Chi Zhu; Ming Wen; Bo Tong; Tao Tian; DuoYan Liao (Journal of Environmental Management, 2025)

Characterization of non-typhoidal Salmonella reveals the highly prevalent mcr-1-positive S. 1,4,[5],12:i:- within eggs are derived from chickens - Ting-Yu Yang; Tiantian Liu; Yan Li; Zeqing Wang; Meijun Chu; Junjie Wang; Ming Zou; Bao-Tao Liu (International Journal of Food Microbiology, 2025)

Enhanced discontinuity characterization in hard rock pillars using point cloud completion and DBSCAN clustering - Chuanqi Li; Jian Zhou; Kun Du; Ming Tao (International Journal of Rock Mechanics and Mining Sciences, 2025)

Deep eutectic solvent-based ultrasonic-assisted extraction of polyphenol from Chenopodium quinoa Willd.: Optimization and lipid-lowering activity - Xiao-tong Lin; Si-xuan Zhou; Zhi-peng Sun; Ming-yuan Cao; Tao Zhou; Li-yan Zhao; Gui-tang Chen (Food Chemistry, 2025)

A super convenient and specific CRISPR/Cas12a diagnostic platform for toxigenic Burkholderia gladioli based on virulence genes - Yu Xie; Li Liu; Xue-Ming Cao; Zuo-Qi Gai; Xu Zhang; Hong-Tao Lei; Zhen-Lin Xu; Xing Shen (Food Control, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Dynamic impact of hillslope landslide sediment transfer to ecological environment recovery in earthquake disturbed area - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Mingwei Li (Bulletin of Engineering Geology and the Environment, 2025)

Anti-Müllerian hormone deficiency leads to two distinct ovarian phenotypes with different alterations of sex hormones in gynogenetic carp - Chun Miao; Zhi Li; Tian-Zi Yao; Ming-Tao Wang; Miao Ding; Xiao-Juan Zhang; Yang Wang; Zhong-Wei Wang; Li Zhou; Jian-Fang Gui; Xi-Yin Li (Aquaculture, 2025)

Understanding the mechanism of microplastic-associated antibiotic resistance genes in aquatic ecosystems: Insights from metagenomic analyses and machine learning - Tengyi Zhu; Shuyin Li; Cuicui Tao; Wenxuan Chen; Ming Chen; Zhiyuan Zong; Yajun Wang; Yi Li; Bipeng Yan (Water Research, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Yeast community in the first-round fermentation of sauce-flavor Baijiu: Source, succession and metabolic function - Zheng-Pei Chen; Qian Cao; Tian-Tian Meng; Wei Shi; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Fu-Wei Chen; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; et al. (Food Research International, 2025)

Radiofrequency affects the decrystallization efficiency and physicochemical properties of rape honey via crystal structure modification and inactivating enzyme - Shi-Ye Luo; Jia-Li Tao; Yan-Xiang Bi; Hong-Wei Xiao; Hua-Lei Chen; Xiang-Xin Li; Yin-Chen Wang; Xiao-Ming Fang (Food Chemistry, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Molecular modifications of Serratia plymuthica sucrose isomerase in Bacillus subtilis to improve its catalytic properties - Chen Liu; Mengli Li; Tao Zhang; Ming Miao (Food Bioscience, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Unveiling specific CO2 trapping sites within MOR zeolite for promoting direct air capture of CO2 - Xiangyou Kong; Junxiao Wu; Shujun Ming; Chunhui Cheng; Qin Wu; Yanlin Wang; Xinnan Li; Lei Pang; Yanbing Guo; Tao Li (Chemical Engineering Journal, 2025)

Phototunable phosphorescence energy transfer based on photodimerization of coumarin-12-crown-4 accelerated by γ-cyclodextrin - Hui-Juan Wang; Yan-Tao Li; Ming-Che Shao; Chang-Shuo Yu; Jin-Yao Yang; Lingyang Liu; Suna Wang; Jianmin Dou (Chemical Engineering Journal, 2025)

Enhancing the sintering stability of NiCo/CeO2-Al2O3 catalyst in dry reforming of methane by shaping the Ostwald ripening diffusion path - Feiyang Yu; Xuyingnan Tao; Haoran Yu; Tingting Zhao; Ming Li; Lvdan Liu; Haiqian Wang (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Progress in Transdifferentiation of Autologous Alternative Cell Sources into Corneal Epithelial Cells - Bei Wang; Jiang-Lan Zhao; Wan-Ying Cai; Gong-Yue Wang; Yu-Zhi Li; Jia-Song Wang; Hua-Tao Xie; Ming-Chang Zhang (Stem Cell Reviews and Reports, 2025)

Dual emission chiral carbon dots as fluorescent probe for fast chiral recognition of tryptophan enantiomers - Qi Wu; Yuan Chen; Yan-Li Wang; Ji-Ying Song; Hai-Tao Lv; Ya-Ming Sun (Analytica Chimica Acta, 2025)

Effect of borehole deviation on raise formation via long-hole raise blasting - Xianyang Qiu; Wenbo Shen; Xiuzhi Shi; Ming Tao; Xiaoyuan Li; Wei Zhi (Tunnelling and Underground Space Technology, 2024)

A comprehensive genetic variant reference for the Chinese population - Tao Jiang; Hongzhe Guo; Yadong Liu; Gaoyang Li; Zhe Cui; Xinran Cui; Yue Liu; Yang Li; Anqi Zhang; Shuqi Cao; Tianyi Zhao; Liran Juan; et al. (Science Bulletin, 2024)

Partial nitrification-denitrification triggered the enhanced nitrogen removal in an integrated internal circulation aerated reactor - Ming Tao; Geng Li; Juan Mao; Feixiang Zan; Xiao Liu; Wei Zhang; Xiaohui Wu; Xiejuan Lu (Journal of Water Process Engineering, 2024)

Hydrogen sulfide alleviates cadmium stress in germinating carrot seeds by promoting the accumulation of proline - Miao Sun; Huan-Xuan Qiao; Tao Yang; Peng Zhao; Jun-Hao Zhao; Jia-Ming Luo; Hai-Ye Luan; Xiang Li; Sheng-Cai Wu; Ai-Sheng Xiong (Journal of Plant Physiology, 2024)

Exploring a maize-derived dietary fiber-phenolic acid complex with prebiotic effects - Yujing Sun; Gaoke Li; Wu Li; Chunyan Li; Tao Zhang; Ming Miao (Food Chemistry, 2024)

Functional characteristics of whole-food arabinoxylans from sweet maize varieties - Yujing Sun; Gaoke Li; Wu Li; Chunyan Li; Tao Zhang; Ming Miao (Food Bioscience, 2024)

Seasonality shapes the microbiota and metabolome of strong-flavor Baijiu during fermentation and affects its flavor characteristics - Li-Juan Chai; Jing-Yi Zhang; Tao Gao; Long-Yun Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Jin-Song Shi; Xiang Chen; Zheng-Hong Xu (Food Bioscience, 2024)

Iterative multimodule reprogramming and protein engineering for efficient lactodifucotetraose bioproduction - Mengli Li; Tao Zhang; Chenchen Li; Ruoyu Jia; Ming Miao (Food Bioscience, 2024)

Recent advances in thermochemical conversion technology for anaerobic digestate from food waste - Changnan Mei; Mingqian Cheng; Ming Xie; Ruihao Yang; Tingting Liu; Zechun Huang; Tao Zhou; Youcai Zhao; Zewei Liu; Bin Li (Bioresource Technology, 2024)

Crop antiviral defense: Past and future perspective - Zhirui Yang; Guangyao Li; Yongliang Zhang; Fangfang Li; Tao Zhou; Jian Ye; Xianbing Wang; Xiaoming Zhang; Zongtao Sun; Xiaorong Tao; Ming Wu; Jianguo Wu; et al. (Science China Life Sciences, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

TG-FTIR-Py-GCMS analysis and catalytic pyrolysis mechanism of textile waste by red mud catalyst for liquid fuel production - Zewei Liu; Yanyu Yang; Ming Xie; Mingqian Cheng; Ruihao Yang; Zechun Huang; Tao Zhou; Youcai Zhao; Jinzhong Yang; Qingqi Die; Bin Li (Science of The Total Environment, 2024)

Decoding the Qu-aroma of medium-temperature Daqu starter by volatilomics, aroma recombination, omission studies and sensory analysis - Sheng-Bing Yang; Jun-Jie Fu; Jia-Huan He; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; Zheng-Hong Xu (Food Chemistry, 2024)

Design of epoxy composites via molecular orbital modulation and enhanced π-πF interactions achieving synchronous improvement of electrical and mechanical performance - Wenxia Sima; Wenlong Pang; Potao Sun; Tao Yuan; Ming Yang; Xiaoxiao Chen; Zhaoping Li; Xiaotong Liu; Xinyu Tang (Chemical Engineering Journal, 2024)

Measurement and Stress Response Analysis of Complete History of Blast-Induced Wall Pressure for Boreholes: A Case with Air-Deck Charge - Qiyue Li; Xinao Wei; Xibing Li; Kai Liu; Longjun Dong; Ming Tao; Haiqian Li (Rock Mechanics and Rock Engineering, 2024)

Anti-adipogenesis and anti-obesity potential of alliin mediated by modulating glycolipid metabolism via activating PPARγ signaling - Ming-Yan Yang; Yu-Jing Liu; Mei-Hua Zheng; Tao Pan; Zhen-Yuan Li; Bai-Fang Gong; Hua-Ying Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Joint effects of air pollution and genetic susceptibility on incident primary open-angle glaucoma - Hao-Neng Huang; Pan-Pan Zhu; Zhou Yang; Yi-Ming Tao; Xiaofeng Ma; Hai-Bing Yu; Li Li; Chun-Quan Ou (Science of The Total Environment, 2024)

Cu inanchored MnO/carbonaceous frameworks trigger peroxymonosulfate activation for enrofloxacin degradation: ROS generation and pollutant attacking processes - Huai-Yuan Niu; Zheng-Tao Dong; Hai Guo; Ya-Ya Yang; Wen-Jie Yang; Ming Yan; Cheng-Gang Niu; Ji-Shan Li (Journal of Environmental Chemical Engineering, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

Comparative genomics of Clostridium tyrobutyricum reveals signatures of environment-specific adaptation and metabolic potentials - Guan-Yu Fang; Li-Juan Chai; Zhen-Ming Lu; Xiao-Juan Zhang; Hong-Yu Xu; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2024)

Characterization of c-Jun N-terminal kinase (JNK) gene reveals involvement of immune defense against Vibrio splendidus infection in Apostichopus japonicus - Wenjun Tao; Weijia Xu; Xin Li; Xiumei Zhang; Chenghua Li; Ming Guo (Fish & Shellfish Immunology, 2024)

A review on catalytic pyrolysis of textile waste to high-value products: Catalytic mechanisms, products application and perspectives - Ming Xie; Mingqian Cheng; Yanyu Yang; Zechun Huang; Tao Zhou; Youcai Zhao; Peiyuan Xiao; Qihong Cen; Zewei Liu; Bin Li (Chemical Engineering Journal, 2024)

Effects of cadmium on the intestinal health of the snail Bradybaena ravida Benson - Yan-Mei Da; Shun-Shun Li; Yan-Qi Li; Le-Yu Deng; Ming-Jun Li; Tao Huang; Qing-Ye Sun; Jazbia Shirin; Guo-Wei Zhou (Ecotoxicology, 2024)

Dietary vitamin B6 could improve the utilization of high carbohydrate diet by promoting carbohydrate degradation and lipid synthesis in Pacific white shrimp (Litopenaeus vannamei) - Xinyue Tao; Tingting Zhu; Ming Li; Jingling Lu; Min Jin; Weijian Liu; Qicun Zhou (Animal Feed Science and Technology, 2024)

ELMO interacts with DOCK180 to enhance coelomocyte phagocytosis in Vibrio splendidus challenged Apostichopus japonicus - Xin Li; Wenjun Tao; Weitao Tu; Yangxi Xiang; Yina Shao; Ming Guo; Chenghua Li (Aquaculture, 2024)

Avermectin induced vascular damage in zebrafish larvae: association with mitochondria-mediated apoptosis and VEGF/Notch signaling pathway - Wei-Guo Wang; Xu-Feng Jiang; Cheng Zhang; Xiu-Ping Zhan; Jia-Gao Cheng; Li-Ming Tao; Wen-Ping Xu; Zhong Li; Yang Zhang (Journal of Hazardous Materials, 2024)

Natural pyrethrins induce cytotoxicity in SH-SY5Y cells and neurotoxicity in zebrafish embryos (Danio rerio) - Wei-Guo Wang; Shou-Lin Li; Bin Liu; Ning Tang; Cheng Zhang; Xu-Feng Jiang; Li-Ming Tao; Wen-Ping Xu; Yang Zhang (Environmental Research, 2024)

A Semi-Supervised Model for Fine-Grained Identification of Oil Emulsions on the Sea Surface Using Hyperspectral Imaging - Ming Xie; Tao Gou; Shuang Dong; Ying Li (Journal of the Indian Society of Remote Sensing, 2024)

Seismic identification and characterization of complex storage space oil and gas reservoirs - XiaoYu-Jiang; Song Tao; Deng-Gan Li; Yue-Zhou Xiao; Liang Jing; Lele-Wei; Zhang Ming; Xiaofeng-Dai (Applied Geophysics, 2024)

A steady-state weight adaptation method for decomposition-based evolutionary multi-objective optimisation - Xiaofeng Han; Tao Chao; Ming Yang; Miqing Li (Swarm and Evolutionary Computation, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

A review on liquid fuel produced from microwave-assisted pyrolysis of plastic waste - Zewei Liu; Ming Xie; Tao Zhou; Jinzhong Yang; Yanyu Yang; Tingting Liu; Shijin Dai; Qifei Huang; Qihong Cen; Peiyuan Xiao; Bin Li; Huanzheng Du (Process Safety and Environmental Protection, 2024)

Adaptive maximum correntropy UKF TDOA tracking algorithm based on multi-layer isogradient sound speed profile - Xulin Liu; Wei Chen; Zewen Tao; Yongqiang Tian; Jianxing Leng; Ming Li; Dazhuan Wu (Ocean Engineering, 2024)

Development of a self-reinforced starch-derived film with biocompatibility and mechanical properties - Liping Wang; Dexiang Li; Lei Ye; Chaohui Zhi; Tao Zhang; Ming Miao (Food Chemistry, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Integrated assessment of trace elements in a marine ranching area based on multi-species and multi-level biomarkers: a case study in China’s national-level marine ranching demonstration area - Mingzhu Li; Zhixu Chen; Ming Li; Jiugang Zhang; Bingqing Xu; Yanyan Yang; Xiangfei Li; Linlin Fan; Baojun Liu; Tao Zheng; Yan Fang; Fan Li (Frontiers in Marine Science, 2024)
The goal of this study was to evaluate the trace element pollution in a marine ranching area in China based on molecular responses (expression of metallothionein and antioxidant enzyme genes), and biochemical biomarkers (metallothionein content, antioxidant enzyme activities, and malonaldehyde level) in four indicator species. We collected samples of two fish ( Lateolabrax maculatus and Sebastes schlegelii ), one crustacean ( Charybdis japonica ), and one gastropod ( Rapana venosa ) from the western Furong Island marine ranching area and from an adjacent area in March 2022 and measured the trace element content in these indicator species as well as in the seawater and sediment. We found that the bioaccumulation characteristics of trace elements and the response patterns of biomarkers were species specific. Moreover, not every biomarker was significantly correlated with environmental trace element content. We then established two biomarker combinations indicative of trace element pollution in seawater and sediment, respectively, based on the correlation between biomarkers and trace element contents. The selected biomarkers were integrated using integrated biomarker response version 2 (IBRv2). IBRv2 values in the studied marine ranching area were lower than those in the adjacent area. Additionally, these values were consistent with the bioaccumulation of trace elements in the indicator species, the integrated trace element pollution index for seawater, and the potential risk index for sediment. These results show that this multi-biomarker and multi-species IBRv2 approach provided a comprehensive diagnosis of trace element pollution in the marine ranching area. Therefore, its application may be beneficial for marine environmental monitoring and management in view of the ecotoxicological impact of pollutants on organisms.

Metabolites assay offers potential solution to improve the rooster semen cryopreservation - Xue Du; Yuanning Zhang; Duoxi Li; Jie Han; Yali Liu; Lijuan Bai; Tao Huang; Ming Cui; Panlin Wang; Xianzhong Zheng; Ayong Zhao (Theriogenology, 2024)

Quantifying energy flexibility potential of ground electric vehicles in an airport with real behavior data - Xiaochen Liu; Ming Li; Xiaohua Liu; Tao Zhang; Zhi Fu; Zhihan Su; Rang Tu (Sustainable Cities and Society, 2024)

Numerical simulation of wedges slamming non-Newtonian fluids based on SPH method - Jie Cui; Qing Yao; Xin Chen; Ming-Yuan Li; De-Tao Xu (Ocean Engineering, 2024)

Extraction and identification of polyphenol from Camellia oleifera leaves using tailor-made deep eutectic solvents based on COSMO-RS design - Shiling Feng; Guanfeng Deng; Huanyao Liu; Haiqiu Shi; Pingjin Li; Xiao Li; Tao Chen; Lijun Zhou; Ming Yuan; Chunbang Ding (Food Chemistry, 2024)

Pu-erh tea-derived cellulose exhibits superior water/oil holding capacity compared to black and green tea celluloses: A comprehensive analysis - Liping Wang; Yukun Li; Lei Ye; Chaohui Zhi; Tao Zhang; Ming Miao (Food Bioscience, 2024)

Akirin2 enhances antibacterial ability via interacting with 14-3-3ζ in V. splendidus-challenged Apostichopus japonicus - Wenjun Tao; Xin Li; Xianmu Fu; Yina Shao; Ming Guo; Chenghua Li (Fish & Shellfish Immunology, 2024)

Co4+ in porous ZIF-67-derives intercalating-bridging adsorption of 2-reaction sites for simultaneous 2-electron transfer toward sensitive detection of uric acid - Li Peng Gan; Juan Li; Fan Shi; Zhuo Zou; Ke Jiang Li; Zhuan Zhuan Shi; Xiao Shuai Wu; Yun Peng Li; Wei Sun; Zhi Song Lu; Tao Hu; Liming Dai; et al. (Analytica Chimica Acta, 2024)

Alkaloids from the stems of Fissistigma maclurei Merr. inhibit the proliferation of synoviocytes - Mu-Tao Liang; Xiao-Zheng Zhang; Zi-Hao Chen; Chuan-Shan Fu; Duo-Jiang Li; Guo-Ze Chen; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

Altered individual gray matter structural covariance networks in early abstinence patients with alcohol dependence - Hai-ling Cao; Ya-jing Meng; Wei Wei; Tao Li; Ming-li Li; Wan-jun Guo (Brain Imaging and Behavior, 2024)

Rapidly count crop seedling emergence based on waveform Method(WM) using drone imagery at the early stage - Jie Yuan; Xu Li; Meng Zhou; Hengbiao Zheng; Zhitao Liu; Yang Liu; Ming Wen; Tao Cheng; Weixing Cao; Yan Zhu; Xia Yao (Computers and Electronics in Agriculture, 2024)

Characterizations and film-forming properties of different fractionated high-amylose maize starches subjected to hydroxypropylation - Liping Wang; Dexiang Li; Lei Ye; Chaohui Zhi; Tao Zhang; Ming Miao (Food Chemistry, 2024)

Mapping and characterization of rust resistance genes Lr53 and Yr35 introgressed from Aegilops species - Binyang Xu; Tao Shen; Hong Chen; Hongna Li; Shams ur Rehman; Shikai Lyu; Lei Hua; Guiping Wang; Chaozhong Zhang; Kairong Li; Hao Li; Caixia Lan; et al. (Theoretical and Applied Genetics, 2024)
Key message The rust resistance genes Lr53 and Yr35 were introgressed into bread wheat from Aegilops longissima or Aegilops sharonensis or their S-genome containing species and mapped to the telomeric region of chromosome arm 6BS. Abstract Wheat leaf and stripe rusts are damaging fungal diseases of wheat worldwide. Breeding for resistance is a sustainable approach to control these two foliar diseases. In this study, we used SNP analysis, sequence comparisons, and cytogenetic assays to determine that the chromosomal segment carrying Lr53 and Yr35 was originated from Ae.longissima or Ae. sharonensis or their derived species. In seedling tests, Lr53 conferred strong resistance against all five Chinese Pt races tested, and Yr35 showed effectiveness against Pst race CYR34 but susceptibility to race CYR32. Using a large population (3892 recombinant gametes) derived from plants homozygous for the ph1b mutation obtained from the cross 98M71 × CS ph1b , both Lr53 and Yr35 were successfully mapped to a 6.03-Mb telomeric region of chromosome arm 6BS in the Chinese Spring reference genome v1.1. Co-segregation between Lr53 and Yr35 was observed within this large mapping population. Within the candidate region, several nucleotide-binding leucine-rich repeat genes and protein kinases were identified as candidate genes. Marker pku6B3127 was completely linked to both genes and accurately predicted the absence or presence of alien segment harboring Lr53 and Yr35 in 87 tetraploid and 149 hexaploid wheat genotypes tested. We developed a line with a smaller alien segment (< 6.03 Mb) to reduce any potential linkage drag and demonstrated that it conferred resistance levels similar to those of the original donor parent 98M71. The newly developed introgression line and closely linked PCR markers will accelerate the deployment of Lr53 and Yr35 in wheat breeding programs.

Maintenance of callus-associated endophyte balance to mitigate oxidative browning in plant tissue culture practices - Yu-Tao Wang; Chun-Xiao Chen; Ping Zhou; Chun-Xi Lu; Yun Wen; Yu Li; Xiao-Xia Pan; Shu-Sheng Zhu; Ming-Zhi Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Recent advances in organic waste pyrolysis and gasification in a CO2 environment to value-added products - Yanyu Yang; Tao Zhou; Mingqian Cheng; Ming Xie; Nan Shi; Tingting Liu; Zechun Huang; Youcai Zhao; Qifei Huang; Zewei Liu; Bin Li (Journal of Environmental Management, 2024)

Delivering cells via ECM mimetic hydrogel microspheres for promoting the reconstruction of rat lumbar nucleus pulposus - Hao Liu; Xin Tian; Chenyang Jin; Yangfeng Li; Xuesong Zhu; Ming Pei; Tao Liu; Huilin Yang; Yong Xu; Fan He (Chemical Engineering Journal, 2024)

An Objective Framework for Bivariate Risk Analysis of Flash Floods Under the Compound Effect of Rainfall Characteristics - Tao Jiang; Qiulian Wei; Ming Zhong; Jianfeng Li (Water Resources Management, 2024)

Identification of sex locus and a male-specific marker in blunt-snout bream (Megalobrama amblycephala) using a whole genome resequencing method - Ming Wen; Siyu Wang; Chunchun Zhu; Yuxin Zhang; Zheng Liu; Chang Wu; Shi Wang; Yude Wang; Li Ren; Min Tao; QinBo Qin; Chun Zhang; et al. (Aquaculture, 2024)

High-throughput analytical methodology of monoalkyl phthalate esters and the composite risk assessment with their parent phthalate esters in aquatic organisms and seawater - Qiang-Qiang Shi; Feng Xu; Tao Shen; Rong-Rong Zhang; Hua Liu; Ming-Ze Chen; Ai-Li Sun; Ze-Ming Zhang; Xi-Zhi Shi (Journal of Hazardous Materials, 2024)

Industrial scale testing on the combustion and NO emission characteristics of ammonia cofiring in a 40 MWth coal-fired boiler - Wenzhen Zhang; Xin Liu; Chaoqun Zhang; Ming Li; Tao Niu; Yan Xie; Heyang Wang (Fuel, 2024)

Water in liquid crystal emulsion-based sensing platform for colorimetric detection of organophosphorus pesticide - Benyou Li; Wenli Wu; Jin-Ming Lin; Tao Wang; Qiongzheng Hu; Li Yu (Food Chemistry, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Designing and preparing supramolecular encapsulation systems based on fraxetin and cyclodextrins for highly selective detection of nicotine - Yun-Han Yang; Zhen Zhang; Qiu-Lian Bao; Fang Zhao; Ming-Kun Yang; Xin Tao; Yan Chen; Jun-Tong Zhang; Li-Juan Yang (Carbohydrate Polymers, 2024)

Effective value-added strategy of furan compounds with short straight-chain monohydric alcohols based on acid site regulation of zirconium based mesoporous carbon - Jian Xiong; Liying Li; Xuebin Lu; Lei Ye; Zhihao Yu; Wei Li; Ming Zhang; Yiming Li; Jiao Tao; Rui Zhang; Yina Qiao (Biomass and Bioenergy, 2024)

Applying teleconnection information to interpret the attributions of urban extreme precipitation - Yuxiang Zhao; Jie Tao; He Li; Qiting Zuo; Pan Liu; Bo Ming (Theoretical and Applied Climatology, 2024)

Associations between metal(loid) exposure with overweight and obesity and abdominal obesity in the general population: A cross-sectional study in China - Tianran Shen; Liling Zhong; Guiyuan Ji; Baolan Chen; Mengfan Liao; Lvrong Li; Huiming Huang; Jiajie Li; Yuan Wei; Shan Wu; Zihui Chen; Wenjun Ma; et al. (Chemosphere, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

CircMETTL7A enhances Toll pathway-mediated innate immunity and antibacterial activity in V. splendidus-challenged Apostichopus japonicus by reducing miR-137 function - Ming Guo; Wenjun Tao; Xianmu Fu; Chenghua Li (Aquaculture, 2024)

Sustainable valorizing high-protein feather waste utilization through solid-state fermentation by keratinase-enhanced Streptomyces sp. SCUT-3 using a novel promoter - Wen-Jun Lu; Ming-Shu Zhang; De-Lin Lu; Zhi-Wei Li; Zhen-Dong Yang; Lei Wu; Jing-Tao Ni; Wei-Dong Chen; Jun-Jin Deng; Xiao-Chun Luo (Waste Management, 2024)

Discovery of bioactive polycyclic polyprenylated acylphloroglucinols with adamantine/homoadamantane skeletons from Hypericum wilsonii - Bo Tao; Yongqi Li; Zhengyi Shi; Yulin Duan; Yi Guo; Xinye Huang; Jie Li; Yeting Zhang; Ming Chen; Fei Song; Xueqi Lan; Weiguang Sun; et al. (Phytochemistry, 2024)

High-temperature interaction mechanisms of typical igniting pyrotechnics with cellulose as the packing material - Xiao-Tao Tian; Yu-Xue Li; Ming-Hui Yu; Bing Xiao; Pei-Jin Liu; Qi-Long Yan (Fuel, 2024)

Community-level bioaugmentation results in enzymatic activity- and aroma-enhanced Daqu through altering microbial community structure and metabolic function - Wen-Hu Liu; Li-Juan Chai; Hong-Mei Wang; Zhen-Ming Lu; Xiao-Juan Zhang; Chen Xiao; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2024)

Nanohybrid dual-network chitosan-based hydrogels: Synthesis, characterization, quicken infected wound healing by angiogenesis and immune-microenvironment regulation - Yifan Liu; Fengxin Zhao; Tao Song; Ming Tang; Luoqiang Tian; Tinghan He; Dongxiao Li; Yumei Xiao; Xingdong Zhang (Carbohydrate Polymers, 2024)

Efficient breeding and growth advantage of all-male population in Lanzhou catfish (Silurus lanzhouensis) - Jun-Sheng Niu; Tao Wang; Zhi Li; Zhong-Wei Wang; Miao Ding; Ming-Tao Wang; Zong-Qiang Lian; Jie Mei; Yang Wang; Li Zhou; Xiao-Juan Zhang; Jian-Fang Gui; et al. (Aquaculture, 2024)

Innovative no-till seeding technology improves yield and nitrogen use efficiency while reducing environmental pressure in wheat after rice harvesting - Miao Liu; Xiaoli Wu; Ming Li; Tao Xiong; Chaosu Li; Yonglu Tang (Soil and Tillage Research, 2024)

Balancing grain yield and environmental performance by optimizing planting patterns of rice-wheat cropping systems - Ming Li; Chaosu Li; Miao Liu; Tao Xiong; Xiaoli Wu; Yonglu Tang (Science of The Total Environment, 2024)

Cobalt-loaded carbon nanofibers as magnetic catalyst for tetracycline degradation through peroxydisulfate activation: Non-radical dominated mechanism - Yifan Wang; Xiaoxuan Kang; Yuting Li; Ruyi Li; Chang Wu; Luyao Wang; Chongqing Wang; Tao Yang; Ming Ge; Zhangxing He (Journal of Water Process Engineering, 2024)

A study on compound flood prediction and inundation simulation under future scenarios in a coastal city - Ming Zhong; Lu Xiao; Xiaodi Li; Yiwen Mei; Tao Jiang; Lixiang Song; Xiaohong Chen (Journal of Hydrology, 2024)

Environmentally friendly super-insulating material with three-dimensional nanoporous structure: A promising candidate for future gas insulated transmission lines and carbon sequestration - Wenxia Sima; Xiaoxiao Chen; Potao Sun; Tao Yuan; Ming Yang; Yongqing Chen; Wenlong Pang; Zhaoping Li (Chemical Engineering Journal, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

FTase inhibitors and cancer: prospects for use in targeted therapies - Ming-tao Xia; Ling Yu; Zhi-wei Yan; You-de Wang; Li-ying Zhang; Guang-xin Miao; Shuai Li (Medicinal Chemistry Research, 2024)

Slope stability calculation based on sparrow search algorithm and Monte Carlo simulation - Li He; Yong-ming Zhao; Bruno Njamba; Yi-he Liu; Hai-tao Xiong (Arabian Journal of Geosciences, 2024)

The effects of Spinosad on zebrafish larvae and THP-1 cells: Associated with immune cell damage and NF-kappa B signaling pathway activation - Wei-Guo Wang; Shou-Qian Xiong; Jin Lu; Lian-Hua Zhu; Cheng Zhang; Jia-Gao Cheng; Zhong Li; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Chemosphere, 2023)

Dietary inositol improved glucose and lipid metabolism mediated by the Insulin-PI3K-Akt signaling pathway in Pacific white shrimp (Litopenaeus vannamei) - Jingjing Lu; Xinyue Tao; Ming Li; Xin Zhang; Qicun Zhou; Jiaxiang Luo; Tingting Zhu; Lefei Jiao; Min Jin (Aquaculture, 2023)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Time-domain numerical simulation for multi-ships moving in waves with forward speed - Mingxin Li; Suyong Pan; Yong Cheng; Zhi-Ming Yuan; Longbin Tao (Ocean Engineering, 2023)

Multiple paternally inherited chloroplast capture events associated with Taxus speciation in the Hengduan Mountains - Han-Tao Qin; Michael Mӧller; Richard Milne; Ya-Huang Luo; Guang-Fu Zhu; De-Zhu Li; Jie Liu; Lian-Ming Gao (Molecular Phylogenetics and Evolution, 2023)

Nonthermal plasma-activated polyvalent cerium-manganese bimetallic (hydro)oxide-functionalized nanographene for the removal of thallium(I) contaminants and mechanism exploration - Dongping Song; Tao Huang; Yinglan Luo; Di Wu; Shouze Li; Yujie Yan; Chaojun Yang; Qi Fang; Yuxing Wang; Yuxuan Feng; Nan Shang; Ming Xia; et al. (Journal of Cleaner Production, 2023)

Energy-efficient fluorine-free electro-refining of crude lead in a green methanesulfonic acid system - You-gang Li; Cong Chang; Jun-jie Qu; Chang-liu Xiang; Tao Luo; Shan-shan Liu; Shuai Li; Sheng-hai Yang; Heng-hui Wang; Xiao-bo Min; Chang-hong Wang; Yong-ming Chen (Journal of Environmental Chemical Engineering, 2023)

Effect of Zirconium modified Y zeolite via in situ synthesis and its regulation on the formation of excellent NiW catalyst for ultra-deep hydrodesulfurization of 4,6-DMDBT - Houxiang Sun; Lei Li; Huabing Zhang; Haiyan Yang; Tao Yang; Mingyong Shu; Zicong Zhong; Ming Yi; Bo Meng (Chemical Engineering Journal, 2023)

The 10 Most Influential Heavy Rain Events in China in 2022: Selection and Evaluation - Ao Li; Hao Yang; Chunguang Cui; Tao Peng; Yishan Liao; Ming Xu; Xiaofang Wang (Journal of Meteorological Research, 2023)

Interference effects on the upstream wave generated by the catamaran moving across a depth change - Mingxin Li; Yi Chen; Zhi-Ming Yuan; Yong Cheng; Longbin Tao (Ocean Engineering, 2023)

Zebrafish nos2a benefits bacterial proliferation via suppressing ROS and inducing NO production to impair the expressions of inflammatory cytokines and antibacterial genes - Si Yao Zheng; Xinbin Shao; Zhitao Qi; Maocang Yan; Min Hui Tao; Xiao Man Wu; Lining Zhang; Jianzhong Ma; An Li; Ming Xian Chang (Fish & Shellfish Immunology, 2023)

Organophosphate esters (OPEs) in a heavily polluted river in South China: Occurrence, spatiotemporal trends, sources, and phase distribution - Yi-Shan Liu; Hui-Ru Li; Zhi-Lang Lao; Sheng-Tao Ma; Zi-Cong Liao; Ai-Min Song; Ming-Yang Liu; You-Sheng Liu; Guang-Guo Ying (Environmental Pollution, 2023)

Perovskites with narrow quantum-wells distribution and thermally activated energy funneling for sky-blue light-emitting diodes - Guanwei Sun; Weidong Qiu; Jiayu Li; Shuai Zhang; Zijian Chen; Denghui Liu; Chenyang Shen; Tao Wen; Zhe Liu; Junrong Pu; Zhihai Yang; Guo-xi Yang; et al. (Chemical Engineering Journal, 2023)

JcSEUSS1 negatively regulates reproductive organ development in perennial woody Jatropha curcas - Jingxian Wang; Xue Bai; Yiqing Su; Hongjun Deng; Li Cai; Xin Ming; Yan-Bin Tao; Huiying He; Zeng-Fu Xu; Mingyong Tang (Planta, 2023)

Ångstrom-scale silver particles ameliorate collagen-induced and K/BxN-transfer arthritis in mice via the suppression of inflammation and osteoclastogenesis - Ze-Hui He; Jing-Tao Zou; Xia Chen; Jiang-Shan Gong; Ya Chen; Ling Jin; Yi-Wei Liu; Shan-Shan Rao; Hao Yin; Yi-Juan Tan; Zun Wang; Wei Du; et al. (Inflammation Research, 2023)

Short-term effect of meteorological factors and extreme weather events on daily outpatient visits for dry eye disease between 2013 and 2020: a time-series study in Urumqi, China - Si-Yu Gui; Fei Wang; Jian-Chao Qiao; Xin-Chen Wang; Zhi-Hao Huang; Fan Yang; Cheng-Yang Hu; Fang-Biao Tao; Li-Ming Tao; Dong-Wei Liu; Xiang-Long Yi; Zheng-Xuan Jiang (Environmental Science and Pollution Research, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Synergistic driving effects of risk factors on human brucellosis in Datong City, China: A dynamic perspective from spatial heterogeneity - Li Shen; Ming-hao Sun; Wen-tao Ma; Qing-wu Hu; Chen-xi Zhao; Zu-rong Yang; Cheng-hao Jiang; Zhong-jun Shao; Kun Liu (Science of The Total Environment, 2023)

Collision avoidance fault-tolerant control for dynamic positioning vessels under thruster faults - Ming-Yang Li; Long-Tao Liu; Wen-Bo Xie; Ji-Tao Li (Ocean Engineering, 2023)

Fate of Cd during mineral transformation by sulfate-reducing bacteria in clay-size fractions from soils with high geochemical background - Xing Yan; Dong-Xing Guan; Jie Li; Yinxian Song; Hua Tao; Xianming Zhang; Ming Ma; Junfeng Ji; Wancang Zhao (Journal of Hazardous Materials, 2023)

Engineering Escherichia coli for the efficient biosynthesis of 6′-sialyllactose - Chenchen Li; Mengli Li; Miaomiao Hu; Wei Gao; Ming Miao; Tao Zhang (Food Bioscience, 2023)

CircRNA254 functions as the miR-375 sponge to inhibit coelomocyte apoptosis via targeting BAG2 in V. splendidus-challenged Apostichopus japonicus - Chuili Zeng; Wenjun Tao; Xianmu Fu; Chenghua Li; Ming Guo (Fish & Shellfish Immunology, 2023)

Wuzi Yanzong Pill relieves MPTP-induced motor dysfunction and neuron loss by inhibiting NLRP3 inflammasome-mediated neuroinflammation - Tao Pan; Qi Xiao; Hui-Jie Fan; Lei Xu; Shao-Chen Qin; Li-Xia Yang; Xiao-ming Jin; Bao-Guo Xiao; Bo Zhang; Cun-Gen Ma; Zhi Chai (Metabolic Brain Disease, 2023)

Exploration of glycosyltransferases mutation status in cervical cancer reveals PARP14 as a potential prognostic marker - Hui Wang; Shen Luo; Xin Wu; Yuanyuan Ruan; Ling Qiu; Hao Feng; Shurong Zhu; Yanan You; Ming Li; Wenting Yang; Yanding Zhao; Xiang Tao; et al. (Glycoconjugate Journal, 2023)
This study investigates the potential role of Glycosyltransferases (GTs) in the glycosylation process and their association with malignant tumors. Specifically, the study focuses on PARP14, a member of GTs, and its potential as a target for tumors in the diagnosis and treatment of cervical cancer. To gather data, the study used somatic mutation data, gene expression data and clinical information from TCGA-CESE dataset as well as tissue samples from cervical cancer patients. Further verification was conducted through RT-qPCR and immunohistochemistry staining on cervical cancer tissues to confirm the expression of PARP14. The study utilized Kaplan-Meier for survival analysis of cervical cancer patient and found significant mutational abnormalities in GTs. The high frequency mutated gene was identified as PARP14. RT-qPCR revealed significantly higher mRNA expression of PARP14 compared to precancerous tissue. Using IHC combined with Kaplan-Meier,patients in the PARP14 high expression group had a better prognosis than the low expression group. The study identified PARP14 as a frequently mutated gene in cervical cancer and proposed its potential role in diagnosis and treatment.

Isolation of tumor stem-like cells from primary laryngeal squamous cell carcinoma cells (FD-LS-6) - Duo Zhang; Di Tang; Pen-tao Liu; Lei Tao; Li-ming Lu (Human Cell, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Perioperative changing patterns and longitudinal trajectories of CA242 with colorectal cancer prognosis: a retrospective longitudinal cohort study - Chunxia Li; Ruimin You; Lizhu Liu; Yanli Li; Hongjiang Pu; Ming Lei; Zhenhui Li; Dingyun You; Qiuxia Xiong; Tao Zhang (Science Bulletin, 2023)

Chemomechanical pretreatment for efficient delignification and saccharification of corn stover biomass - Samuel Ntakirutimana; Tao Xu; Ming-Zhu Ding; Zhi-Hua Liu; Bing-Zhi Li; Ying-Jin Yuan (Chemical Engineering Journal, 2023)

Human milk oligosaccharide lacto-N-tetraose: Physiological functions and synthesis methods - Miaomiao Hu; Ming Miao; Kewen Li; Qingmin Luan; Guilian Sun; Tao Zhang (Carbohydrate Polymers, 2023)

Enhancement of electrokinetic-phytoremediation by Ophiopogon japonicus: stimulation of electrokinetic on root system and improvement of polycyclic aromatic hydrocarbon degradation - Ming Li; Yingping Huang; Kun Li; Xi Yuan; Huigang Liu; Meng Li; Tao Xu; Zhaonian Zhang; David M. Johnson; Ying Xi (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Anti-apoptotic effect of adrenomedullin gene delivery on Leydig cells by suppressing TGF-β1 via the Hippo signaling pathway - You-wen Luo; Xia-lian Zhu; Ming-yong Li; Jian-hua Zhou; Zhi-min Yang; Tao Tong; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2023)

Dual-modular immunosensor for bongkrekic acid detection using specific monoclonal antibody - Xue-Ming Cao; Li-Hua Li; Hong-Zhi Liang; Jia-Dong Li; Zi-Jian Chen; Lin Luo; Yi-Na Lu; Yu-Xin Zhong; Yu-Dong Shen; Hong-Tao Lei; Hong Wang; Zhen-Lin Xu (Journal of Hazardous Materials, 2023)

Emerging roles of air pollution and meteorological factors in autoimmune eye diseases - Fan Cao; Zhuo-Ran Liu; Qin-Yu Ni; Chen-Kai Zha; Shu-Jie Zhang; Jia-Min Lu; Yue-Yang Xu; Li-Ming Tao; Zheng-Xuan Jiang; Hai-Feng Pan (Environmental Research, 2023)

The health risk of acetochlor metabolite CMEPA is associated with lipid accumulation induced liver injury - Wei-Guo Wang; Mu-Yao Li; Lin Diao; Cheng Zhang; Li-Ming Tao; Wei-Xing Zhou; Wen-Ping Xu; Yang Zhang (Environmental Pollution, 2023)

High prevalence and genomic characteristics of carbapenem-resistant Enterobacteriaceae and colistin-resistant Enterobacteriaceae from large-scale rivers in China - Cai-Hong Guo; Yu-Qing Liu; Yan Li; Xiao-Xiao Duan; Ting-Yu Yang; Fang-Yu Li; Ming Zou; Bao-Tao Liu (Environmental Pollution, 2023)

Atmospheric humidity regulates same-sex mating in Candida albicans through the trehalose and osmotic signaling pathways - Chao Li; Li Tao; Guobo Guan; Zhangyue Guan; Austin M. Perry; Tianren Hu; Jian Bing; Ming Xu; Clarissa J. Nobile; Guanghua Huang (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Structural classification of EZH2 inhibitors and prospects for the treatment of tumor: a review - Ling Yu; Ming-tao Xia; You-de Wang; Zhi-wei Yan; Li-ying Zhang; Shuai Li (Medicinal Chemistry Research, 2023)

A review on intelligent impedance cytometry systems: Development, applications and advances - Tao Tang; Trisna Julian; Doudou Ma; Yang Yang; Ming Li; Yoichiroh Hosokawa; Yaxiaer Yalikun (Analytica Chimica Acta, 2023)

Machine learning models to predict the tunnel wall convergence - Jian Zhou; Yuxin Chen; Chuanqi Li; Yingui Qiu; Shuai Huang; Ming Tao (Transportation Geotechnics, 2023)

Origin and diversification of a Himalayan orchid genus Pleione - Sha-Sha Wu; Ming-Tao Jiang; Jiang-lin Miao; Ming-He Li; Jie-Yu Wang; Li-Ming Shen; Dong-Hui Peng; Si-Ren Lan; Jun-Wen Zhai; Zhong-Jian Liu (Molecular Phylogenetics and Evolution, 2023)

Synergistic effects of pyrolysis temperature, iron ion concentration and solid/liquid ratio on the properties and Cr(VI) removal performance of magnetic carbon - Qiang Qu; Ling Qiu; Ming-Zhuo Li; Guo-Tao Sun; He-Yu Chen; Xiao-Hui Guo (Journal of Water Process Engineering, 2023)

Potential of derivation of a series of C6–C14 1-alkene skeletal oxidation mechanisms on the basis of reaction rate rules - Shuai Huang; Yachao Chang; Ming Jia; Rui Hu; Tao Li (Fuel, 2023)

A system for inspecting karst voids during construction of cast-in-place pile foundations - Liu Liu; Zhenming Shi; Shaojun Li; Ming Peng; Fengjuan Tao (Engineering Geology, 2023)

Enhancing thermoelectric performance of n-type Bi2Te2.7Se0.3 through the incorporation of MnSb2Se4 nanoinclusions - Tao Chen; Xiaoying Qin; Hongwei Ming; Xuemei Zhang; Ziyuan Wang; Shuhuan Yang; Yongsheng Zhang; Zhenhua Ge; Hongxing Xin; Di Li; Jian Zhang (Chemical Engineering Journal, 2023)

Beta-naphthoflavone increases the differentiation of osteoblasts and suppresses adipogenesis in human adipose derived stem cells involving STAT3 pathway - Ming Lu; Min Li; Tao Luo; Yongsui Li; Mingxin Wang; Huashi Xue; Mengchen Zhang; Qiu Chen (Molecular & Cellular Toxicology, 2023)

The combined effect of seawater salinity and duration on the survival and growth of eelgrass Zostera marina - Yan-Hao Zhang; Jian-Du Li; Wen-Jie Yan; Fan-Shu Luo; Li Wang; Li-Ming Zuo; Jun-Ge Xu; Wen-Tao Li; Pei-Dong Zhang (Aquatic Botany, 2023)

Heterogeneous photo-Fenton degradation of acid orange 7 activated by red mud biochar under visible light irradiation - Kun Lin; Shahzad Afzal; Liheng Xu; Tao Ding; Feng Li; Ming Zhang (Environmental Pollution, 2023)

Integrated intelligent tactile system for a humanoid robot - Rongrong Bao; Juan Tao; Jing Zhao; Ming Dong; Jing Li; Caofeng Pan (Science Bulletin, 2023)

Wash waves generated by ship moving across a depth change - Mingxin Li; Zhi-Ming Yuan; Longbin Tao (Ocean Engineering, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

Machine learning based age-authentication assisted by chemo-kinetics: Case study of strong-flavor Chinese Baijiu - Qing-Ru Liu; Xiao-Juan Zhang; Lei Zheng; Lian-Jun Meng; Guang-Qian Liu; Ting Yang; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Cai-Hong Shen; Zheng-Hong Xu (Food Research International, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Ensemble learning system to identify nutritional risk and malnutrition in cancer patients without weight loss information - Liangyu Yin; Jie Liu; Ming Liu; Jin Zheng; Aiguo Xu; Quanjun Lyu; Yongdong Feng; Zengqing Guo; Hu Ma; Jipeng Li; Zhikang Chen; Hui Wang; et al. (Science China Life Sciences, 2023)

Chemical constituents and biological activities of Artemisia argyi H.Lév. & vaniot - Yun-hong Zhang; Zhu-tao Shao; Guang-ming Bi; Yi-wei Sun; Yu-meng Wang; Da-li Meng (Natural Product Research, 2023)

Preparation and characterization of carboxymethyl chitosan/pullulan composite film incorporated with eugenol and its application in the preservation of chilled meat - Zhen Zeng; Yu-Jing Yang; Qian Tu; Yu-Ying Jian; Da-Ming Xie; Ting Bai; Shan-Shan Li; Yun-Tao Liu; Cheng Li; Cai-Xia Wang; Ai-Ping Liu (Meat Science, 2023)

Bacteria and filamentous fungi running a relay race in Daqu fermentation enable macromolecular degradation and flavor substance formation - Wen-Hu Liu; Li-Juan Chai; Hong-Mei Wang; Zhen-Ming Lu; Xiao-Juan Zhang; Chen Xiao; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2023)

Inhibition of ferroptosis by icariin treatment attenuates excessive ethanol consumption-induced atrial remodeling and susceptibility to atrial fibrillation, role of SIRT1 - Li-Ming Yu; Xue Dong; Tao Huang; Ji-Kai Zhao; Zi-Jun Zhou; Yu-Ting Huang; Yin-Li Xu; Qiu-Sheng Zhao; Zhi-Shang Wang; Hui Jiang; Zong-Tao Yin; Hui-Shan Wang (Apoptosis, 2023)

CDK8 mediates coelomocyte proliferation via promoting β-catenin nuclear translocation in Vibrio splendidus-challenged Apostichopus japonicus - Chuili Zeng; Wenjun Tao; Bangping Hu; Ming Guo; Chenghua Li (Aquaculture, 2023)

Adaptive reinforcement learning fault-tolerant control for AUVs With thruster faults based on the integral extended state observer - Zhifu Li; Ming Wang; Ge Ma; Tao Zou (Ocean Engineering, 2023)

Early Neoproterozoic well-preserved stromatolites from southern Liaoning, North China: characteristics and paleogeographic implications - Yong-Li Zhang; Guan-Ming Lai; En-Pu Gong; Mark A. Wilson; Wen-Tao Huang; Chang-Qing Guan; Ding-Cheng Yuan (Palaeoworld, 2023)

Evidence of hydrothermal fluid migration pathways in pores and microfractures based on nuclear magnetic resonance and electron microscopic analyses from the Southwest Indian Ridge - Qianyu Li; Chao Chen; Chunhui Tao; Tao Wu; Jianping Zhou; Zhaoyang Su; Zhongmin Zhu; Long Liu; Tianyu Jie; Ming Chen (Marine Geology, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

A novel Stauntonia leucantha fruits arabinogalactan: isolation and structural characterization - Hui Li; Tao Gao; Zhonghao Zhang; Jiangping Lei; Junchao Hu; Zizhong Tang; Shiling Feng; Chunbang Ding; Tao Chen; Yanger Chen; Shu Yuan; Ming Yuan (Carbohydrate Polymers, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

The galU gene is required for in vivo survival of pseudomonas plecoglossicida in large yellow croaker ( Larimichthys crocea ) - Feng‐Ling Shu; Li‐Yun Jin; Hao Liu; Zhen Tao; Fei Yin; Jia‐Song Xie; Su‐Ming Zhou (Journal of Fish Diseases, 2023)
Pseudomonas plecoglossicida is an important pathogenic bacterium in aquaculture that causes visceral granulomas in large yellow croaker ( Larimichthys crocea ). Uridine diphosphate glucose phosphorylase encoded by galU plays a key role in biosynthesis of the bacterial envelope, particularly lipopolysaccharide and the capsule. In this study, we inactivated the galU gene in the P. plecoglossicida isolate XSDHY‐P. The galU mutant strain showed impaired growth in the early exponential stage and lacked the O polysaccharide side chain in lipopolysaccharide, but almost no defect in biofilm formation was detected. The galU mutant strain also exhibited significantly more sensitivity to the bactericidal action of normal fish serum mediated by the complement system compared to the wild‐type strain. In a cell model originating from the head kidney of large yellow croaker, the galU mutant strain showed lower capacities of adhesion, invasion, and intracellular survival compared to the wild‐type strain. In addition, the deficiency of the galU mutant drastically decreased bacterial loads in tissues and attenuated P. plecoglossicida virulence in fish. These results suggest that the galU gene of P. plecoglossicida is required for in vivo survival in large yellow croaker.

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Huntingtin-associated protein 1 is a potential tumor suppressor for gastric cancer - Ye-Min Qu; Ai Chen; Xue Zhao; Zan Wang; Dong Guo; Shu-Li Shao; Yuan-Yong Tao; Qiu-Jing Li; Ming-Yi Wang; Wan-Shan Ma (Molecular Biology Reports, 2023)

Low soil moisture suppresses the thermal compensatory response of microbial respiration - Jin‐Tao Li; Yan Zhang; Hongyang Chen; Huiming Sun; Weitao Tian; Jinquan Li; Xiang Liu; Shurong Zhou; Changming Fang; Bo Li; Ming Nie (Global Change Biology, 2023)
The thermal compensatory response of microbial respiration contributes to a decrease in warming‐induced enhancement of soil respiration over time, which could weaken the positive feedback between the carbon cycle and climate warming. Climate warming is also predicted to cause a worldwide decrease in soil moisture, which has an effect on the microbial metabolism of soil carbon. However, whether and how changes in moisture affect the thermal compensatory response of microbial respiration are unexplored. Here, using soils from an 8‐year warming experiment in an alpine grassland, we assayed the thermal response of microbial respiration rates at different soil moisture levels. The results showed that relatively low soil moisture suppressed the thermal compensatory response of microbial respiration, leading to an enhanced response to warming. A subsequent moisture incubation experiment involving off‐plot soils also showed that the response of microbial respiration to 100 d warming shifted from a slight compensatory response to an enhanced response with decreasing incubation moisture. Further analysis revealed that such respiration regulation by moisture was associated with shifts in enzymatic activities and carbon use efficiency. Our findings suggest that future drought induced by climate warming might weaken the thermal compensatory capacity of microbial respiration, with important consequences for carbon–climate feedback.

circRNA1149 from Apostichopus japonicus suppresses coelomocyte apoptosis act as miR-92a sponge to regulate Bax expression in response to Vibrio splendidus infection - Ming Guo; Yankai Wang; Xianmu Fu; Wenjun Tao; Chenghua Li (Aquaculture, 2023)

Biogenetic peloidal micrites within coral skeletons cause geochemical anomalies in reef limestones, Zhongsha Atoll, South China Sea - Hong-Qiang Yang; Xi-Yang Zhang; Yue Li; Qi Shi; Shi-Chen Tao; Xi-Nan Mu; Ming-Zhuang Wang; Xiao-Ju Liu; Fei Tan; Sheng-Nan Zhou; Guan Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Efficient adsorption removal of NO2 by covalent triazine frameworks with fine-tuned binding sites - Yuanmeng Tian; Ming Kong; Zeyu Tao; Chen Yang; Shanshan Shang; Qinfen Gu; Daniel C.W. Tsang; Liangchun Li; Jin Shang (Journal of Hazardous Materials, 2023)

An investigation into the effect of water injection parameters on synergetic mining of geothermal energy in mines - Yu Xu; Zijun Li; Ming Tao; Saeid Jalilinasrabady; Junjian Wang; Gang Li; Kaiqi Zhong (Journal of Cleaner Production, 2023)

Freezing-induced loss of wheat starch granule-associated proteins affected dough quality: From water distribution, rheological properties, microstructure, and gluten development - Han Tao; Fan Lu; Xue-Feng Zhu; Hui-Li Wang; Xue-Ming Xu (Journal of Cereal Science, 2023)

Corrigendum to “Irinotecan decreases intestinal UDP-glucuronosyltransferase (UGT) 1A1 via TLR4/MyD88 pathway prior to the onset of diarrhea” [Food Chem. Toxicol. 166 (2022) 113246] - Gabriel Tao; Fatima Dagher; Li Li; Rashim Singh; Ming Hu; Romi Ghose (Food and Chemical Toxicology, 2023)

Enhanced phonon scattering and thermoelectric performance for N-type Bi2Te2.7Se0.3 through incorporation of conductive polyaniline particles - Shuhuan Yang; Hongwei Ming; Di Li; Tao Chen; Shujin Li; Jian Zhang; Hongxing Xin; Xiaoying Qin (Chemical Engineering Journal, 2023)

Passivation of positively charged cationic defects in perovskite with nitrogen-donor crown ether enabling efficient perovskite solar cells - Yuxuan Yang; Tao Zhao; Ming-Hua Li; Xiaoxue Wu; Mingyue Han; Shih-Chi Yang; Qiaoling Xu; Lede Xian; Xiang Chi; Ning-Jiu Zhao; Hong Cui; Sihan Li; et al. (Chemical Engineering Journal, 2023)

Damage evolution and strength attenuation characteristics of carbonaceous slate under low velocity dynamic impact - Zhi-gang Tao; Meng-nan Li; Kui-ming Liu; Kai-wen Ai; Yong Wang (Journal of Mountain Science, 2023)

Sensitivity analysis of seismic attributes and oil reservoir predictions based on jointing wells and seismic data – A case study in the Taoerhe Sag, China - Na Li; Jinliang Zhang; Jun Matsushima; Cheng Song; Xuwei Luan; Ming Dou; Tao Chen; Lingling Wang (Frontiers in Marine Science, 2022)
It is important to identify the location of gravelly sandstone in Taoerhe Sag, an oil target area in the Chezhen Depression. To date, most attention has focused on sedimentary characteristics; hence, information regarding a clear sensitivity analysis of seismic attributes is incomplete. To address this, we used well analysis and seismic attribute interpretation to find sensitive seismic attributes and sand bodies. Based on the well analysis and core data, a geologicald model of mudstone and sandstone was established, and the electrical characteristics of three kinds of lithology were identified. We used correlation analysis to select the optimal logging parameters and seismic attributes to identify sandstone. We used multi-attribute fusion technology and stratigraphic slices to characterize the spatial distribution characteristics of gravelly sandstone in the target area and used genetic algorithm inversion volume to evaluate the prediction results. The results indicate that the three main lithologies of the lower submember of Shahejie Formation 3 (P 2 S 3 X ) in the Taoerhe Sag can be distinguished by natural gamma (GR), acoustic time difference (AC) and saturated hydrocarbon content (SH) logging curves. The seismic attribute characteristics of gravelly sandstone of P 2 S 3 X are high root mean square amplitude (RMS) values, high instantaneous bandwidth (BW) values, low 3D curvature (Curv) values, medium-high instantaneous phase (Phase) values and high instantaneous frequency (Freq) values. In this study, we found two nearshore underwater fans in P 2 S 3 X . Gravelly sandstone is located along the slope zone and the lake bottom, with a total sedimentary area of 57.9 km 2 . The method summarized in this paper can be applied to other similar deep-water basins.

Palmitoylation of MDH2 by ZDHHC18 activates mitochondrial respiration and accelerates ovarian cancer growth - Xuan Pei; Kai-Yue Li; Yuan Shen; Jin-Tao Li; Ming-Zhu Lei; Cai-Yun Fang; Hao-Jie Lu; Hui-Juan Yang; Wenyu Wen; Miao Yin; Jia Qu; Qun-Ying Lei (Science China Life Sciences, 2022)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Key factors affecting carbon prices from a time-varying perspective - Ming-Fang LI; Hui HU; Lu-Tao ZHAO (Environmental Science and Pollution Research, 2022)

Chloride-binding capacity of mortars composed of marine sand subjected to external chloride penetration - Congtao Sun; Ming Sun; Tao Tao; Feng Qu; Gongxun Wang; Peng Zhang; Yantao Li; Jizhou Duan (Journal of Oceanology and Limnology, 2022)

Dioxin emission and distribution from cement kiln co-processing of hazardous solid waste - Wen-Wen Ye; Peng-Tao Cai; Ming-Xiu Zhan; Wen-Tao Jiao; Xu-Xu; Jian-Ying Fu; Tong Chen; Xiao-Dong Li (Environmental Science and Pollution Research, 2022)

Increases in temperature response to CO2 emissions in biochar-amended vegetable field soil - Rong Huang; Zifang Wang; Yi Xiao; Luo Yu; Xuesong Gao; Changquan Wang; Bing Li; Qi Tao; Qiang Xu; Ming Gao (Environmental Science and Pollution Research, 2022)

Diversity and Structure of Demersal Fish Community Over the Northern Slope in the South China Sea - Jun Zhang; Kui Zhang; Yan-e Jiang; Yuan-jie Li; Jiang-tao Fan; Wen-ming Yu; Zuo-zhi Chen (Frontiers in Marine Science, 2022)
Three bottom trawl surveys over the northern continental slope in the South China Sea (18°50′–20°40′N, 112°50′–115°10′E) were carried out, in June 2015, March 2017 and September 2018, to investigate species composition, biodiversity and community structure of demersal fish. Surveys in 2015, 2017 and 2018 captured 97 fish species (representing 77 genera, 52 families, 26 orders), 108 fish species (representing 84 genera, 61 families, 19 orders) and 126 fish species (representing 105 genera, 74 families, 25 orders), respectively. Three surveys captured a total of 252 fish species, representing 164 genera, 97 families, 30 orders. Perciformes dominated. Species richness in station linking shallow continental shelf with deep slope was the lowest among stations. In three surveys, 16 species occurred in the catches of three surveys, accounting for 6.35% of all species. Species replacement rate between stations showed a significant linear relationship with the depth difference and latitude difference. Margalef’s species richness index ( D ), Shannon–Weiner diversity index ( H’ ) and Pielou’s evenness index ( J’ ) among stations ranged 2.65–6.74, 1.02–4.15 and 0.28–1.14, respectively. Differences of D , H ’ and J ’ were insignificant among seasons. There were significant positive linear relations between H’ and J’ and latitude. D , H’ and J’ decreased with increasing sampling depth, however the relations were not significant. Based on multivariate statistical analysis, fish community at species level was divided into five groups with average dissimilarities of 95.69%–99.96%. In terms of genus and family, average dissimilarities among groups were more than 88.11% and 82.69%. There were significant differences in species composition between depths, but no significant differences between seasons and temperatures, as well as in genus and family composition.

Association between meteorological factors and hospital admissions for uveitis in Hefei, China: a time-series study - Fan Cao; Yi-Sheng He; Kun Xiang; Cheng-Huan Wan; Wei Liu; Yan-Chao Gui; Hai-Feng Pan; Zheng-Xuan Jiang; Li-Ming Tao (Environmental Science and Pollution Research, 2022)

FLO8 deletion leads to decreased adhesion and virulence with downregulated expression of EPA1, EPA6, and EPA7 in Candida glabrata - Jun-Tao Zhao; Ke-Zhi Chen; Jin-Yan Liu; Wei-Hua Li; Yu-Zhu Wang; Lu-Ling Wang; Ming-Jie Xiang (Brazilian Journal of Microbiology, 2022)

Comparison of different inversion methods of D-T2 two-dimensional nuclear magnetic resonance logging and applicability analysis - Cheng-Lin Li; Mao-Jin Tan; Ke-Wen Wang; Feng Zhou; Ying-Ming Liu; Hai-Tao Zhang; Li-Zhi Xiao (Applied Geophysics, 2022)

Quinolizidine alkaloids from the roots of Sophora flavescens - Jian-Chun Li; Zhi-Jun Zhang; Dan Liu; Ming-Yan Jiang; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2022)

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats - Dan Ren; Jia-Ni Li; Xin-Tong Qiu; Fa-Ping Wan; Zhen-Yu Wu; Bo-Yuan Fan; Ming-Ming Zhang; Tao Chen; Hui Li; Yang Bai; Yun-Qing Li (Neuroscience Bulletin, 2022)
Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant increase in FOS-expressing neurons in the nucleus tractus solitarii (NTS) and ACC, and some FOS-expressing neurons in the NTS projected to the ACC. In addition, a larger portion of ascending fibers from the NTS innervated pyramidal neurons, the neural subpopulation primarily expressing FOS under the condition of painful CP, rather than GABAergic neurons within the ACC. CP rats showed increased expression of vesicular glutamate transporter 1, and increased membrane trafficking and phosphorylation of the N -methyl-D-aspartate receptor (NMDAR) subunit NR2B and the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluR1 within the ACC. Microinjection of NMDAR and AMPAR antagonists into the ACC to block excitatory synaptic transmission significantly attenuated abdominal hyperalgesia in CP rats, which was similar to the analgesic effect of endomorphins injected into the ACC. Specifically inhibiting the excitability of ACC pyramidal cells via chemogenetics reduced both hyperalgesia and comorbid anxiety, whereas activating these neurons via optogenetics failed to aggravate hyperalgesia and anxiety in CP rats. Taken together, these findings provide neurocircuit, biochemical, and behavioral evidence for involvement of the ACC in hyperalgesia and anxiety in CP rats, as well as novel insights into the cortical modulation of painful CP, and highlights the ACC as a potential target for neuromodulatory interventions in the treatment of painful CP.

Transgelin-2 interacts with CD44 to regulate Notch1 signaling pathway and participates in colorectal cancer proliferation and migration - Rong Ding; Guoyu Li; Yueyi Yao; Lijuan Zhang; Xuan Zhang; Jiayi Li; Tao Shen; Yi Gao; Tao Wu; Shuzhen Kong; Ming Huang; Yunfeng Li (Journal of Physiology and Biochemistry, 2022)

Flavobacterium proteolyticum sp. nov., isolated from aquaculture water - Juan Du; Yang Liu; Tao Pei; Anzhang Li; Ming-Rong Deng; Honghui Zhu (Archives of Microbiology, 2022)

Glutamatergic Neurons in the Caudal Zona Incerta Regulate Parkinsonian Motor Symptoms in Mice - Li-Xuan Li; Yu-Lan Li; Jin-Tao Wu; Ji-Zhou Song; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Near-epicenter weather conditions several hours before strong earthquakes (Ms ≥ 6) - Tao Chen; Lei Li; Xiao-Xin Zhang; Qi-Ming Ma; Wen Li; Shuo Ti; Han Wu; Ren-Kang Li; Jing Luo; Jian-Feng Su (Natural Hazards, 2022)

Colorado geoid computation experiment: overview and summary - Yan Ming Wang; Laura Sánchez; Jonas Ågren; Jianliang Huang; René Forsberg; Hussein A. Abd-Elmotaal; Kevin Ahlgren; Riccardo Barzaghi; Tomislav Bašić; Daniela Carrion; Sten Claessens; Bihter Erol; et al. (Journal of Geodesy, 2021)

Characterization of the novel hybrid cultivar E25 of Saccharina japonica in the northern farming region of China - Li Su; Ti Feng Shan; Jing Li; Su Qin Gao; Shao Jun Pang; Xiao Fei Leng; Yan Zhang; Ming Fu Zhang; Hong Tao Gao (Journal of Applied Phycology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Functional homoeologous alleles of CONSTANS contribute to seasonal crop type in rapeseed - Qingdong Jin; Shuai Yin; Ge Li; Tao Guo; Ming Wan; Haitao Li; Juanjuan Li; Xianhong Ge; Graham J. King; Zaiyun Li; Jing Wang; Guangsheng Zhou (Theoretical and Applied Genetics, 2021)

Influence of algal blooms on the efficacy of La/Al-based phoslock in the control of phosphorus release from sediment in shallow lakes: a microcosm study - Tianlun Han; Ming Kong; Chenjie Tang; Xueting Xu; Yanzhong Zhu; Yuexiang Gao; Tao Zhang; Yimin Zhang; Weixin Li (Journal of Soils and Sediments, 2021)

Microseismic source location method based on a velocity model database and statistical analysis - Bing-Rui Chen; Tao Li; Xin-Hao Zhu; Fan-Bo Wei; Xu Wang; Ming-Xing Xie (Arabian Journal of Geosciences, 2021)

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

A fungal sirtuin modulates development and virulence in the insect pathogen, Beauveria bassiana - Qing Cai; Li Tian; Jia‐Tao Xie; Qiu‐Ying Huang; Ming‐Guang Feng; Nemat O. Keyhani (Environmental Microbiology, 2021)
Summary Chromatin transitions are mediated in part by acetylation/deacetylation post‐translational modifications of histones. Histone deacetylases, e.g. sirtuins (Sir‐proteins), repress transcription via promotion of heterochromatin formation. Here, we characterize the Sir2 class III histone deacetylase ( BbSir2 ) in the environmentally and economically important fungal insect pathogen, Beauveria bassiana . BbSir2 is shown to contribute to the deacetylation of lysine residues on H3 and H4 histones. Targeted gene knockout of BbSir2 resulted in impaired asexual development, reduced abilities to utilize various carbon/nitrogen sources, reduced tolerance to oxidative, heat, and UV stress, and attenuated virulence. ΔBbSir2 cells showed disrupted cell cycle development and abnormal hyphal septation patterns. Proteomic protein acetylation analyses of wild type and ΔBbSir2 cells revealed the differential abundance of 462 proteins and altered (hyper‐ or hypo‐) acetylation of 436 lysine residues on 350 proteins. Bioinformatic analyses revealed enrichment in pathways involved in carbon/nitrogen metabolism, cell cycle control and cell rescue, defence and mitochondrial functioning. Critical targets involved in virulence included LysM effector proteins and a benzoquinone oxidoreductase implicated in detoxification of cuticular compounds. These data indicate broad effects of BbSir2 on fungal development and stress response, with identification of discrete targets that can account for the observed (decreased) virulence phenotype.

Tracing Nutrients and Organic Matter Changes in Eutrophic Wenchang (China) and Oligotrophic Krka (Croatia) Estuaries: A Comparative Study - You-You Hao; Zhuo-Yi Zhu; Fu-Tao Fang; Tihana Novak; Milan Čanković; Enis Hrustić; Zrinka Ljubešić; Ming Li; Jin-Zhou Du; Rui-Feng Zhang; Blaženka Gašparović (Frontiers in Marine Science, 2021)
Estuaries modify the concentration and composition of riverine nutrients and organic matter (OM), which eventually determine the riverine flux effect to coasts. Nutrients, organic carbon (OC), pigments, and amino acids (AAs) from the samples collected in the eutrophic Wenchang River Estuary (WRE) in China and the oligotrophic Krka River Estuary (KRE) in Croatia were analyzed in order to have a better understanding of how estuaries regulate terrestrial materials. We found a clear increase of dissolved inorganic nitrogen (DIN) concentration and its subsequent decrease due to the removal of DIN (over 100 μM) in the WRE, whereas DIN showed minor variation lengthwise in the KRE, i.e., with the salinity changes, ranging between 1.0 and 5.8 μM. The elevated algae-derived OC, dissolved organic nitrogen, and particulate AAs nitrogen suggest that the OM assimilation may explain approximately one-third of the DIN removal in the WRE, whereas in the oligotrophic KRE, such inorganic to organic transformation is not likely to be significant. Due to the prominent estuarine nitrogen removal/assimilation process, DIN/dissolved inorganic phosphorus (DIP) ratio was as high as 425 in the upper WRE under strong riverine influence, but it declined to as low as 5.4 at the mouth of WRE, that is even lower than DIN/DIP ratio at the mouth of oligotrophic KRE (12). When compared with other rivers worldwide, the Wenchang River showed high nutrients and organic carbon yields. Given the contrasting estuarine process (e.g., DIN removal) between the KRE and the WRE, apparent high nutrient yield from eutrophic rivers should be viewed with caution in ocean studies as the final impact to coastal zone could be similar to the oligotrophic rivers like the KRE.

Synthesis and biological evaluation of novel 1,3-diphenylurea quinoxaline derivatives as potent anticancer agents - Gui-Zhen Li; Xi-Lin Ouyang; Zu-Yu Mo; Yao Gu; Xiao-Lin Cao; Li Yang; Hai-Tao Tang; Ying-Ming Pan (Medicinal Chemistry Research, 2021)

OsGSTU6 Contributes to Cadmium Stress Tolerance in Rice by Involving in Intracellular ROS Homeostasis - Xiu-Qing Jing; Meng-Ru Zhou; Xiu-Min Nie; Lu Zhang; Peng-Tao Shi; Abdullah Shalmani; Hai Miao; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2021)

Isolation and Identification of Pseudomonas sp. Strain DY-1 from Agricultural Soil and Its Degradation Effect on Prometryne - Dong Liang; Ming-yue Ding; Chang-yixin Xiao; Ya-wen Shen; Yin-yue Wang; Hai-tao Li; Rong-mei Liu; Ji-guo Gao (Current Microbiology, 2021)

Shear strength and microstructure of silty clay subjected to CaSO4 solution and stability effect on a gypsum dump - Tao Wei; Guoqing Chen; Xiang Sun; Yang Li; Changan Qin; Ming Yan (Bulletin of Engineering Geology and the Environment, 2021)

Nitrogen removal performance and bacterial communities in zeolite trickling filter under different influent C/N ratios - Lina Liu; Na Li; Chunyang Tao; Yubo Zhao; Jingqing Gao; Zhenzhen Huang; Jingshen Zhang; Jianlei Gao; Jinliang Zhang; Ming Cai (Environmental Science and Pollution Research, 2021)

Thermaurantiacus tibetensis gen. nov., sp. nov., a novel moderately thermophilic bacterium isolated from hot spring microbial mat in Tibet - Yu-Zhen Ming; Lan Liu; Ai-Ping Lv; Wen-Dong Xian; Ze-Tao Liu; Meng-Meng Li; Jian-Yu Jiao; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Spatial distribution of atmospheric bioaerosols in Beijing, Hangzhou and Wuhan, China - Xuezheng Ma; Qi Zhang; Keyang Liu; Liping Zhang; Manman Zhang; Xin Zhao; Chunya Zhou; Jinke Li; Ming Cheng; Lili Li; Kongxin Hu; Jinsong Li; et al. (Aerobiologia, 2021)

Phylogenetic analysis of infectious bronchitis virus circulating in southern China in 2016–2017 and evaluation of an attenuated strain as a vaccine candidate - Libin Chen; Bin Xiang; Yanfen Hong; Qian Li; Haoyun Du; Qiuyan Lin; Ming Liao; Tao Ren; Chenggang Xu (Archives of Virology, 2021)

OsRbohB-mediated ROS production plays a crucial role in drought stress tolerance of rice - Yi Shi; Yan-Li Chang; Hai-Tao Wu; Abdullah Shalmani; Wen-Ting Liu; Wen-Qiang Li; Jian-Wei Xu; Kun-Ming Chen (Plant Cell Reports, 2020)

New potential strains for controlling Spodoptera frugiperda in China: Cordyceps cateniannulata and Metarhizium rileyi - Ye-Ming Zhou; Wen Xie; Jia-Qin Ye; Tao Zhang; Ding-Yin Li; Jun-Rui Zhi; Xiao Zou (BioControl, 2020)

Effects of the Lower Airway Secretions on Airway Opening Pressures and Suction Pressures in Critically Ill COVID-19 Patients: A Computational Simulation - Zhenglong Chen; Ming Zhong; Li Jiang; Nanshan Chen; Shengjin Tu; Yuan Wei; Ling Sang; Xia Zheng; Chunyuan Zhang; Jiale Tao; Linhong Deng; Yuanlin Song (Annals of Biomedical Engineering, 2020)

Multiple environmental factors analysis of flash flood risk in Upper Hanjiang River, southern China - Ming Zhong; Tao Jiang; Kun Li; Qiaoqian Lu; Jiao Wang; Jiajun Zhu (Environmental Science and Pollution Research, 2020)

Postchemotherapy hippocampal functional connectivity patterns in patients with breast cancer: a longitudinal resting state functional MR imaging study - Yun Feng; Dilihumaer Tuluhong; Zhao Shi; Li Juan Zheng; Tao Chen; Guang Ming Lu; Shaohua Wang; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

TMEM88 modulates the secretion of inflammatory factors by regulating YAP signaling pathway in alcoholic liver disease - Liang-yun Li; Chen-chen Yang; Su-wen Li; Yu-min Liu; Hao-dong Li; Shuang Hu; Hong Zhou; Jin-liang Wang; Hang Shen; Xiao-ming Meng; Jun Li; Tao Xu (Inflammation Research, 2020)

Microvirga arsenatis sp. nov., an arsenate reduction bacterium isolated from Tibet hot spring sediments - Ze-Tao Liu; Wen-Dong Xian; Meng-Meng Li; Lan Liu; Yu-Zhen Ming; Jian-Yu Jiao; Bao-Zhu Fang; Min Xiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2020)

Identification of QTLs for resistance to leaf spots in cultivated peanut (Arachis hypogaea L.) through GWAS analysis - Hui Zhang; Ye Chu; Phat Dang; Yueyi Tang; Tao Jiang; Josh Paul Clevenger; Peggy Ozias-Akins; Corley Holbrook; Ming Li Wang; Howard Campbell; Austin Hagan; Charles Chen (Theoretical and Applied Genetics, 2020)

The role of miRNA-155 in monocrotaline-induced pulmonary arterial hypertension through c-Fos/NLRP3/caspase-1 - Shou-Dong Chai; Zhen-Kun Li; Rui Liu; Tao Liu; Ming-Feng Dong; Pei-Zhe Tang; Jian-Tang Wang; Sheng-Jun Ma (Molecular & Cellular Toxicology, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Correction to: Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)

Optimization of an mRNA vaccine assisted with cyclodextrin-polyethyleneimine conjugates - Lu Tan; Tao Zheng; Man Li; Xiaofang Zhong; Yao Tang; Ming Qin; Xun Sun (Drug Delivery and Translational Research, 2020)

N-Glycoproteome Reveals That N-Glycosylation Plays Crucial Roles in Photosynthesis and Carbon Metabolism in Young Rice Leaves - Jiafeng Wang; Hui Wen; Ming Li; Tao Guo; Chun Chen (Journal of Plant Biology, 2020)

Experimental and finite element analysis of marble with double pre-existing flaws under loading-unloading conditions - Yan-qi Song; Xiang-shang Li; Tao Zhou; Ming Li (Arabian Journal of Geosciences, 2020)

Fractionation and chemical structure of dissolved organic matter in the rhizosphere associated with cadmium accumulation in tobacco lines (Nicotiana tabacum L.) - Ming Zhao; Tingxuan Li; Haiying Yu; Xizhou Zhang; Zicheng Zheng; Yongdong Wang; Tao Liu; Dharmendra K. Gupta; Huagang Huang (Environmental Science and Pollution Research, 2020)

Genome-Wide Identification of Malectin/Malectin-Like Domain Containing Protein Family Genes in Rice and Their Expression Regulation Under Various Hormones, Abiotic Stresses, and Heavy Metal Treatments - Xiu-Qing Jing; Abdullah Shalmani; Meng-Ru Zhou; Peng-Tao Shi; Izhar Muhammad; Yi Shi; Rahat Sharif; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2020)

Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)
Simulated microgravity can significantly affect various cell types and multiple systems of the human body, such as cardiovascular system, skeletal muscle system, and immune system, and is known to cause anemia and loss of electrolyte and fluids. Epidermal stem cells (EpSCs) were cultured in a rotary cell culture system (RCCS) bioreactor to simulate microgravity. The metabolites of EpSCs were identified by liquid chromatography-mass spectrometry (LC-MS). Compared with normal gravity (NG) group, a total of 57 different metabolites of EpSCs were identified ( P < 0.05, VIP > 1), including lipids and lipid-like molecules (51 molecules), amino acids (5 molecules), nucleosides, nucleotides, and analogues (1 molecule). According to the partial least squares discriminant analysis (PLS-DA) score plot, a VIP > 1 and P < 0.05 were obtained for the 57 different metabolites, of which 23 molecules were significantly downregulated and 34 were significantly upregulated in simulated microgravity (SMG) group. These results showed that SMG has a significant impact on different pathways, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis indicated that multiple pathways were involved, mainly the amino acid metabolism pathway, lipid metabolism pathway, membrane transport pathway, and cell growth and death pathways. Thus, the metabolic profile of EpSCs was changed under SMG. Exploring the metabolic profile of EpSCs would be helpful to further understand the growth characteristics of EpSCs under SMG, which will provide a new approach to explore the metabolomics mechanism of stress injury and repair trauma under SMG.

The variation of motor-related brain structure and its relation to abnormal motor behaviors in end-stage renal disease patients with restless legs syndrome - Junya Mu; Xiaohui Liu; Shaohui Ma; Tao Chen; Xueying Ma; Peng Li; Dun Ding; Jixin Liu; Ming Zhang (Brain Imaging and Behavior, 2020)

Effectiveness analysis of the prediction of regional debris flow susceptibility in post-earthquake and drought site - Ning-sheng Chen; Yong Zhang; Shu-feng Tian; Ming-feng Deng; Tao Wang; Li-hong Liu; Mei Liu; Gui-sheng Hu (Journal of Mountain Science, 2020)

Analysing post-earthquake landslide susceptibility using multi-temporal landslide inventories — a case study in Miansi Town of China - Ning Li; Chuan Tang; Tao Yang; Ming Chen (Journal of Mountain Science, 2020)

Evidence for the paternal mitochondrial DNA in the crucian carp-like fish lineage with hybrid origin - Shi Wang; Ni Jiao; Lu Zhao; Meiwen Zhang; Pei Zhou; Xuexue Huang; Fangzhou Hu; Conghui Yang; Yuqin Shu; Wuhui Li; Chun Zhang; Min Tao; et al. (Science China Life Sciences, 2020)

The application of the ‘Gene-deletor’ technology in banana - Chun-hua Hu; Qiao-song Yang; Xiu-hong Shao; Tao Dong; Fang-cheng Bi; Chun-yu Li; Gui-ming Deng; Yi Li; Gan-jun Yi; Tong-xin Dou (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Banana ( Musa spp.) is an important tropical crop. Banana industry is under biotic and abiotic stresses such as Fusarium wilt, typhoon, cold stress. Genetic engineering offers a powerful strategy to create germplasm of banana with enhanced resistance. The safety of genetically modified organisms has become a bottleneck restricting the popularization and application of genetically modified technology. In this study, a candidate promoter, LEAFY (LFY) for expression and flower initiation in Arabidopsis , was cloned and constructed to ‘Gene-deletor’ vector. Histochemical β-glucuronidase (GUS) staining results showed that the ‘Gene-deletor’ vector driven by LFY promoter could lead to 88.5% excision efficiency from Arabidopsis seeds based on more than 200 T 3 progeny examined per event. GUS staining was found to be partially negative in transgenic bananas, however, polymerase chain reaction could still detect the presence of large fragments of the vector. These results suggest that although LFY promoter could not completely drive the ‘Gene-deletor’ vector to achieve the effect of complete elimination of exogenous gene in bananas, its efficiency of eliminating exogenous gene laid a theoretical foundation for cloning banana fruit-specific promoters, that is, ‘non-transgenic’ GM bananas.

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Sulforaphane inhibits the activation of hepatic stellate cell by miRNA-423-5p targeting suppressor of fused - Ming-Hui Feng; Jian-Wei Li; Hai-Tao Sun; Song-Qi He; Jie Pang (Human Cell, 2019)

Use of thermal imaging and Fourier transform infrared spectroscopy for the pre-symptomatic detection of cucumber downy mildew - Dong-Mei Wen; Mei-Xiang Chen; Li Zhao; Tao Ji; Ming Li; Xin-Ting Yang (European Journal of Plant Pathology, 2019)

Benzopyran derivatives from endophytic Daldinia eschscholzii JC-15 in Dendrobium chrysotoxum and their bioactivities - Ming Hu; Xue-Qiong Yang; Qing-Yan Zhou; Shu-Quan Li; Bang-Yan Wang; Bao-Hui Ruan; Ya-Bin Yang; Zhuo-Xi Zhang; Hao Zhou; Zhong-Tao Ding (Natural Product Research, 2019)

Neuroprotective Influence of miR-301a Inhibition in Experimental Cerebral Ischemia/Reperfusion Rat Models Through Targeting NDRG2 - Tao Feng; Bang-Hua Han; Gong-Li Yang; Chao-Jie Shi; Zhen-Wen Gao; Ming-Zhi Cao; Xiao-Lei Zhu (Journal of Molecular Neuroscience, 2019)

Forensic characteristics and phylogenetic structure of Eastern Chinese Han populations residing along the Yangtze Basin revealed by 19 autosomal STR loci - Ruiyang Tao; Shouyu Wang; Ming Jin; Yanting Liu; Jiashuo Zhang; Suhua Zhang; Chengtao Li (Molecular Biology Reports, 2019)

Antioxidant and α -glucosidase inhibitory ingredients identified from Jerusalem artichoke flowers - Yan-Ming Wang; Jian-Qiang Zhao; Jun-Li Yang; Pema Tsering Idong; Li-Juan Mei; Yan-Duo Tao; Yan-Ping Shi (Natural Product Research, 2019)

Two new 2-arylbenzofurnan derivatives from the leaves of Morus alba - Xuewei Wu; Ming Li; Xiaoning Wang; Tao Shen; Shuqi Wang; Dongmei Ren (Natural Product Research, 2019)

Correlation between S100A11 and the TGF-β1/SMAD4 pathway and its effects on the proliferation and apoptosis of pancreatic cancer cell line PANC-1 - Yi-Fei Ji; Tao Li; Feng Jiang; Wen-Kai Ni; Cheng-Qi Guan; Zhao-Xiu Liu; Cui-Hua Lu; Run-Zhou Ni; Wei Wu; Ming-Bing Xiao (Molecular and Cellular Biochemistry, 2019)

Cloning and Identification of Differentially Expressed Genes Associated with Smut in Sugarcane - Xiu-Peng Song; Dan-Dan Tian; Ming-Hui Chen; Zhen-Qiang Qin; Jin-Ju Wei; Chun-Yan Wei; Xiao-Qiu Zhang; De-Wei Li; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2018)

Bacillus methylotrophicus CSY-F1 alleviates drought stress in cucumber (Cucumis sativus) grown in soil with high ferulic acid levels - Xinwei Hou; Fenghui Wu; Xiu-Juan Wang; Zhong-Tao Sun; Yue Zhang; Ming-Tao Yang; Hongrui Bai; Songwen Li; Ji-Gang Bai (Plant and Soil, 2018)

TMEM88 mediates inflammatory cytokines secretion by regulating JNK/P38 and canonical Wnt/β-catenin signaling pathway in LX-2 cells - Tao Xu; Lin-xin Pan; Yun-xuan Ge; Peng Li; Xiao-ming Meng; Cheng Huang; Jun Li (Inflammopharmacology, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Precipitation characteristics over the steep slope of the Himalayas in rainy season observed by TRMM PR and VIRS - Yunfei Fu; Xiao Pan; Tao Xian; Guosheng Liu; Lei Zhong; Qi Liu; Rui Li; Yu Wang; Ming Ma (Climate Dynamics, 2018)

Abnormal interaction between cognitive control network and affective network in patients with end-stage renal disease - Junya Mu; Tao Chen; Qianqian Liu; Dun Ding; Xueying Ma; Peng Li; Anmao Li; Mingxia Huang; Zengjun Zhang; Jixin Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

Experimental Study of the Triaxial Strength Properties of Hollow Cylindrical Granite Specimens Under Coupled External and Internal Confining Stresses - Shaofeng Wang; Xibing Li; Kun Du; Shanyong Wang; Ming Tao (Rock Mechanics and Rock Engineering, 2018)

The breast milk lead levels among Chinese population - Tao Li; Xu-wei Tao; Shuai-ming Zhang; Yao-hua Dai (Environmental Science and Pollution Research, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

Alteration of SlYABBY2b gene expression impairs tomato ovary locule number and endogenous gibberellin content - Hui Li; Mei-hua Sun; Ming-fang Qi; Jiao Xing; Tao Xu; Han-ting Liu; Tian-lai Li (Journal of Zhejiang University-SCIENCE B, 2018)

Early warning model for slope debris flow initiation - Ming-li Li; Yuan-jun Jiang; Tao Yang; Qiang-bing Huang; Jian-ping Qiao; Zong-ji Yang (Journal of Mountain Science, 2018)

Immune responses of mature chicken bone-marrow-derived dendritic cells infected with Newcastle disease virus strains with differing pathogenicity - Bin Xiang; Wenxian Zhu; Yaling Li; Pei Gao; Jianpeng Liang; Di Liu; Chan Ding; Ming Liao; Yinfeng Kang; Tao Ren (Archives of Virology, 2018)

Fast local wavenumber (FLW) method for the inversion of magnetic source parameters - Guo-Qing Ma; Yan-Bo Ming; Jiang-Tao Han; Li-Li Li; Qing-Fa Meng (Applied Geophysics, 2018)

The key gluconeogenic gene PCK1 is crucial for virulence of Botrytis cinerea via initiating its conidial germination and host penetration - Jian‐Kang Liu; Hao‐Wu Chang; Yue Liu; Yu (Haity) Qin; Yu‐Han Ding; Lan Wang; Yue Zhao; Ming‐Zhe Zhang; Sheng‐Nan Cao; Le‐Tao Li; Wei Liu; Gui‐Hua Li; et al. (Environmental Microbiology, 2018)
Summary The process of initiation of host invasion and survival of some foliar phytopathogenic fungi in the absence of external nutrients on host leaf surfaces remains obscure. Here, we demonstrate that gluconeogenesis plays an important role in the process and nutrient‐starvation adaptation before the pathogen host invasion. Deletion of phosphoenolpyruvate c arboxy k inase gene BcPCK1 in gluconeogenesis in Botrytis cinerea , the causative agent of grey mould, resulted in the failure of the Δ Bcpck1 mutant conidia to germinate on hard and hydrophobic surface and penetrate host cells in the absence of glucose, reduction in conidiation and slow conidium germination in a nutrient‐rich medium. The wild‐type and Δ Bcpck1 conidia germinate similarly in the presence of glucose (higher concentration) as the sole carbon source. Conidial glucose‐content should reach a threshold level to initiate germination and host penetration. Infection structure formation by the mutants displayed a glucose‐dependent fashion, which corresponded to the mutant virulence reduction. Exogenous glucose or complementation of BcPCK1 completely rescued all the developmental and virulence defects of the mutants. Our findings demonstrate that BcPCK1 plays a crucial role in B. cinerea pathogenic growth and virulence, and provide new insights into gluconeogenesis mediating pathogenesis of plant fungal pathogens via initiation of conidial germination and host penetration.

Two novel compounds from the root bark of Morus alba L. - Ming Li; Xuewei Wu; Xiaoning Wang; Tao Shen; Dongmei Ren (Natural Product Research, 2018)

Phytotoxic, antibacterial, and antioxidant activities of mycotoxins and other metabolites from Trichoderma sp. - Ju-cheng Zhang; Guang-Yi Chen; Xiao-Zhan Li; Ming Hu; Bang-Yan Wang; Bao-Hui Ruan; Hao Zhou; Li-Xing Zhao; Jun Zhou; Zhong-Tao Ding; Ya-Bin Yang (Natural Product Research, 2017)

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

Low Serum Levels of Brain-Derived Neurotrophic Factor Were Associated with Poor Short-Term Functional Outcome and Mortality in Acute Ischemic Stroke - Jing Wang; Li Gao; Yan-Long Yang; Yu-Qian Li; Tao Chang; Ming-Hao Man; Xing-Ye Zhang; Shao-Chun Guo; Li-Hong Li (Molecular Neurobiology, 2017)

High total volatile organic compounds pollution in a hospital dental department - Ming-Hui Liu; Tao-Hsin Tung; Fen-Fang Chung; Li-Chuan Chuang; Gwo-Hwa Wan (Environmental Monitoring and Assessment, 2017)

Testing of antiviral characteristics of flammutoxin in transgenic tobacco - Li-Ping Wu; Xue-Ling Gao; Yuan-Dan Duan; Ye-Yu Bian; Tao Yang; Ming-Jia Fu (Journal of Plant Diseases and Protection, 2017)

Low genetic diversity and functional constraint of miRNA genes participating pollen–pistil interaction in rice - Kun Wang; Xin Wang; Ming Li; Tao Shi; Pingfang Yang (Plant Molecular Biology, 2017)

Identification of a Bipolar Disorder Vulnerable Gene CHDH at 3p21.1 - Hong Chang; Lingyi Li; Tao Peng; Maria Grigoroiu-Serbanescu; Sarah E. Bergen; Mikael Landén; Christina M. Hultman; Andreas J. Forstner; Jana Strohmaier; Julian Hecker; Thomas G. Schulze; Bertram Müller-Myhsok; et al. (Molecular Neurobiology, 2017)

Chimeras Linked to Tandem Repeats and Transposable Elements in Tetraploid Hybrid Fish - Lihai Ye; Ni Jiao; Xiaojun Tang; Yiyi Chen; Xiaolan Ye; Li Ren; Fangzhou Hu; Shi Wang; Ming Wen; Chun Zhang; Min Tao; Shaojun Liu (Marine Biotechnology, 2017)

Effects of a dark septate endophyte (DSE) on growth, cadmium content, and physiology in maize under cadmium stress - Yongmei He; Zhixin Yang; Mingrui Li; Ming Jiang; Fangdong Zhan; Yanqun Zu; Tao Li; Zhiwei Zhao (Environmental Science and Pollution Research, 2017)

Response of linear and cyclic electron flux to moderate high temperature and high light stress in tomato - Tao Lu; Jie-wei Shi; Zhou-ping Sun; Ming-fang Qi; Yu-feng Liu; Tian-lai Li (Journal of Zhejiang University-SCIENCE B, 2017)

Separation of antioxidant and α -glucosidase inhibitory flavonoids from the aerial parts of Asterothamnus centrali - asiaticus - Yan-Ming Wang; Jian-Qiang Zhao; Jun-Li Yang; Yan-Duo Tao; Li-Juan Mei; Yan-Ping Shi (Natural Product Research, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Molecular characterization and expression of the GDF9 gene in New Zealand white rabbits - Caixia Sun; Shuyu Xie; Tao Huang; Wei Zhang; Ansi Wang; Dan Wang; Ming Li; Guirong Sun (Journal of Genetics, 2017)

Koninginins R-S from the endophytic fungus Trichoderma koningiopsis - Ming Hu; Qi-Ling Li; Ya-Bin Yang; Kai Liu; Cui-Ping Miao; Li-Xing Zhao; Zhong-Tao Ding (Natural Product Research, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Incentive effect of bentonite and concrete admixtures on stabilization/solidification for heavy metal-polluted sediments of Xiangjiang River - Ming Yan; Guangming Zeng; Xiaoming Li; Jianmin He; Guiqiu Chen; Danlian Huang; Lin Tang; Cui Lai; Chang Zhang; Xiaodong Li; Lichao Wang; Zhi Guo; et al. (Environmental Science and Pollution Research, 2017)

Erratum to: Chryseobacterium zhengzhouense sp. nov., isolated from groundwater of a well in a vegetable field - Ya-Nan Wang; Wei-Hong He; Ming-Li An; Wen-Yu Tian; Xiao-Yan You; Fang-Qing Ying; Jing Guo; Tao Gong (Antonie van Leeuwenhoek, 2017)

Sugar Industry and Improved Sugarcane Farming Technologies in China - Yang-Rui Li; Xiu-Peng Song; Jian-Ming Wu; Chang-Ning Li; Qiang Liang; Xi-Hui Liu; Wei-Zan Wang; Hong-Wei Tan; Li-Tao Yang (Sugar Tech, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Spatial characteristics of extreme rainfall over China with hourly through 24-hour accumulation periods based on national-level hourly rain gauge data - Yongguang Zheng; Ming Xue; Bo Li; Jiong Chen; Zuyu Tao (Advances in Atmospheric Sciences, 2016)
Hourly rainfall measurements of 1919 national-level meteorological stations from 1981 through 2012 are used to document, for the first time, the climatology of extreme rainfall in hourly through 24-h accumulation periods in China. Rainfall amounts for 3-, 6-, 12- and 24-h periods at each station are constructed through running accumulation from hourly rainfall data that have been screened by proper quality control procedures. For each station and for each accumulation period, the historical maximum is found, and the corresponding 50-year return values are estimated using generalized extreme value theory. Based on the percentiles of the two types of extreme rainfall values among all the stations, standard thresholds separating Grade I, Grade II and Grade III extreme rainfall are established, which roughly correspond to the 70th and 90th percentiles for each of the accumulation periods. The spatial characteristics of the two types of extreme rainfall are then examined for different accumulation periods. The spatial distributions of extreme rainfall in hourly through 6-h periods are more similar than those of 12- and 24-h periods. Grade III rainfall is mostly found over South China, the western Sichuan Basin, along the southern and eastern coastlines, and in the large river basins and plains. There are similar numbers of stations with Grade III extreme hourly rainfall north and south of 30°N, but the percentage increases to about 70% south of 30°N as the accumulation period increases to 24 hours, reflecting richer moisture and more prolonged rain events in southern China. Potential applications of the extreme rainfall climatology and classification standards are suggested at the end.

Dynamic Brazilian Splitting Test of Ring-Shaped Specimens with Different Hole Diameters - Xibing Li; Qiuhong Wu; Ming Tao; Lei Weng; Longjun Dong; Yang Zou (Rock Mechanics and Rock Engineering, 2016)

Determination of Dynamic Flexural Tensile Strength of Thermally Treated Laurentian Granite Using Semi-Circular Specimens - Tubing Yin; Pin Wang; Xibing Li; Bangbiao Wu; Ming Tao; Ronghua Shu (Rock Mechanics and Rock Engineering, 2016)

Chryseobacterium zhengzhouense sp. nov., isolated from groundwater of the well in a vegetable field, and emended description of the genus Chryseobacterium - Ya-Nan Wang; Wei-Hong He; Ming-Li An; Wen-Yu Tian; Xiao-Yan You; Fang-Qing Ying; Jing Guo; Tao Gong (Antonie van Leeuwenhoek, 2016)

Experimental Study of Slabbing and Rockburst Induced by True-Triaxial Unloading and Local Dynamic Disturbance - Kun Du; Ming Tao; Xi-bing Li; Jian Zhou (Rock Mechanics and Rock Engineering, 2016)

3D finite-difference modeling algorithm and anomaly features of ZTEM - Tao Wang; Han-Dong Tan; Zhi-Qiang Li; Kun-Peng Wang; Zhi-Ming Hu; Xing-Dong Zhang (Applied Geophysics, 2016)

A new isocoumarin from the aerial parts of Aconitum gymnandrum - Jian-Qiang Zhao; Yan-Ming Wang; Shuo Wang; Jun Dang; Yan-Ping Shi; Li-Juan Mei; Yan-Duo Tao (Natural Product Research, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

A new flavone C -glycoside and a new bibenzyl from Bulbophyllum retusiusculum - Ming-Hui Yang; Yun-Shan Fang; Le Cai; Ying Li; Jian-Wei Dong; Tian-Peng Yin; Cai-Li Huang; Zhong-Tao Ding (Natural Product Research, 2016)

Erratum to: Investigation of one-lung ventilation postoperative cognitive dysfunction and regional cerebral oxygen saturation relations - Xi-ming Li; Feng Li; Zhong-kai Liu; Ming-tao Shao (Journal of Zhejiang University-SCIENCE B, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Calpain-Dependent ErbB4 Cleavage Is Involved in Brain Ischemia-Induced Neuronal Death - Ying-mei Lu; Yin-ping Gao; Rong-rong Tao; Mei-hua Liao; Ji-yun Huang; Gang Wu; Feng Han; Xiao-ming Li (Molecular Neurobiology, 2016)

Late Pleistocene - Holocene slip history of the Langshan-Seertengshan piedmont fault (Inner Mongolia, northern China) from cosmogenic 10Be dating on a bedrock fault scarp - Xiao-ming Shen; De-wen Li; Yun-tao Tian; Yan-wu Lv; Da-wei Li; Yan-feng Li (Journal of Mountain Science, 2016)

Procalcitonin Is a Stronger Predictor of Long-Term Functional Outcome and Mortality than High-Sensitivity C-Reactive Protein in Patients with Ischemic Stroke - Chao Wang; Li Gao; Zhi-Guo Zhang; Yu-Qian Li; Yan-Long Yang; Tao Chang; Long-Long Zheng; Xing-Ye Zhang; Ming-Hao Man; Li-Hong Li (Molecular Neurobiology, 2016)

Effects of Freshwater Releases on the Delivery of Ecosystem Services in Coastal Wetlands of the Yellow River Delta Using an Improved Input-State-Output Approach - Ming Li; Wei Yang; Tao Sun (Wetlands, 2016)

Inhibition of IRF3 expression reduces TGF-β1-induced proliferation of hepatic stellate cells - Ming-ming Ni; Tao Xu; Ya-rui Wang; Ying-hua He; Qun Zhou; Cheng Huang; Xiao-ming Meng; Jun Li (Journal of Physiology and Biochemistry, 2016)

Identification and mapping of Tril, a homeodomain-leucine zipper gene involved in multicellular trichome initiation in Cucumis sativus - Yun-Li Wang; Jing-tao Nie; Hui-Ming Chen; Chun-li Guo; Jian Pan; Huan-Le He; Jun-Song Pan; Run Cai (Theoretical and Applied Genetics, 2016)

Identification and Functional Analysis of the NADK Gene Family in Wheat - Xiang Wang; Wen-Yan Li; Mao-Mao Zhang; Yin-Tao Gao; Wen-Ting Liu; Wen-Qiang Li; Izhar Muhammad; Kun-Ming Chen (Plant Molecular Biology Reporter, 2016)

Investigation of one-lung ventilation postoperative cognitive dysfunction and regional cerebral oxygen saturation relations - Xi-ming Li; Feng Li; Zhong-kai Liu; Ming-tao Shao (Journal of Zhejiang University-SCIENCE B, 2015)

Soil labile organic carbon fractions in rhizosphere soil in citrus plantations in the Three Gorges Reservoir Area - Guo-Mei Jia; Bao-Lin Zhang; Jun-Tao Niu; Li-Ming Wang; Fang-Qing Chen (Agroforestry Systems, 2015)

Using hybrid transcription factors to study gene function in rice - Tao Zhao; Jun Liu; Hong-Yu Li; Jian-Zhong Lin; Ming-Di Bian; Chun-Yu Zhang; Yong-Xing Zhang; Yu-Chong Peng; Bin Liu; ChenTao Lin (Science China Life Sciences, 2015)

Orientation selectivity in cat primary visual cortex: local and global measurement - Tao Xu; Hong-Mei Yan; Xue-Mei Song; Ming Li (Neuroscience Bulletin, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

De novo transcriptome assembly of Ipomoea nil using Illumina sequencing for gene discovery and SSR marker identification - Changhe Wei; Xiang Tao; Ming Li; Bin He; Lang Yan; Xuemei Tan; Yizheng Zhang (Molecular Genetics and Genomics, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

NMDAR-Mediated Hippocampal Neuronal Death is Exacerbated by Activities of ASIC1a - Su Gao; Yang Yu; Zhi-Yuan Ma; Hui Sun; Yong-Li Zhang; Xing-Tao Wang; Chaoyun Wang; Wei-Ming Fan; Qing-Yin Zheng; Chun-Lei Ma (Neurotoxicity Research, 2015)

Two genes conferring resistance to Pythium stalk rot in maize inbred line Qi319 - Feng-Jing Song; Ming-Gang Xiao; Can-Xing Duan; Hong-Jie Li; Zhen-Dong Zhu; Bao-Tao Liu; Su-Li Sun; Xiao-Fei Wu; Xiao-Ming Wang (Molecular Genetics and Genomics, 2015)

Chemical constituents from Piper wallichii - Yan-Ni Shi; Lian Yang; Jin-Hua Zhao; Yi-Ming Shi; Yan Qu; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Xing-Cong Li; Min Xu; Ying-Jun Zhang (Natural Product Research, 2015)

Apolipoprotein E gene polymorphisms associated with processing speed and executive functions in healthy Han Chinese - Cheng-Cheng Zhang; Hong-Yan Ren; Ming-Li Li; Qiang Wang; Wei Deng; Wan-Jun Guo; Wei Lei; Bo Xiang; Lian-Sheng Zhao; Xiao-Hong Ma; Yong-Gang Yao; Tao Li (Neuroscience Bulletin, 2015)

Soil pH determines the alpha diversity but not beta diversity of soil fungal community along altitude in a typical Tibetan forest ecosystem - Jun-Tao Wang; Yuan-Ming Zheng; Hang-Wei Hu; Li-Mei Zhang; Jing Li; Ji-Zheng He (Journal of Soils and Sediments, 2015)

Transient receptor potential vanilloid 4 inhibits rat HSC-T6 apoptosis through induction of autophagy - Lei Zhan; Yang Yang; Tao-Tao Ma; Cheng Huang; Xiao-Ming Meng; Lei Zhang; Jun Li (Molecular and Cellular Biochemistry, 2015)

Preparation and Characterization of a Novel Extracellular Polysaccharide with Antioxidant Activity, from the Mangrove-Associated Fungus Fusarium oxysporum - Yan-Li Chen; Wen-Jun Mao; Hong-Wen Tao; Wei-Ming Zhu; Meng-Xia Yan; Xue Liu; Tian-Tian Guo; Tao Guo (Marine Biotechnology, 2015)

ACE2 and Ang-(1–7) protect endothelial cell function and prevent early atherosclerosis by inhibiting inflammatory response - Yue-Hui Zhang; Yong-huan Zhang; Xue-Fei Dong; Qing-Qing Hao; Xiao-Ming Zhou; Qing-Tao Yu; Shu-Ying Li; Xu Chen; Abdulai Fallah Tengbeh; Bo Dong; Yun Zhang (Inflammation Research, 2015)

Relationship Between the DPD and TS mRNA Expression and the Response to S-1-Based Chemotherapy and Prognosis in Patients with Advanced Gastric Cancer - Xiao-Ming Shen; Chong Zhou; Lian Lian; Li-Qun Li; Wei Li; Min Tao (Cell Biochemistry and Biophysics, 2015)

Effects of Exogenous Abscisic Acid on Cell Membrane and Endogenous Hormone Contents in Leaves of Sugarcane Seedlings under Cold Stress - Xing Huang; Ming-Hui Chen; Li-Tao Yang; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2015)

Molecular Cloning and Functional Analysis of an Ethylene Receptor Gene from Sugarcane (Saccharum spp.) by Hormone and Environmental Stresses - Ai-Qin Wang; Xing-Zhi Ye; Jing-Li Huang; Jun-Qi Niu; Ming Liu; Yong-Bao Pan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Morphological changes in gray matter volume correlate with catechol-O-methyl transferase gene Val158Met polymorphism in first-episode treatment-naïve patients with schizophrenia - Ming-Li Li; Bo Xiang; Yin-Fei Li; Xun Hu; Qiang Wang; Wan-Jun Guo; Wei Lei; Chao-Hua Huang; Lian-Sheng Zhao; Na Li; Hong-Yan Ren; Hui-Yao Wang; et al. (Neuroscience Bulletin, 2015)

Synthesis and in vitro antiproliferative activity of novel benzisoselenazolone derivatives - Li-na Xuan; Peng Wang; Kai Zhang; Yan-ping Shi; Yu-ming Liu; Tao Zhu; Bao-quan Chen (Medicinal Chemistry Research, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

A convenient four-component one-pot synthesis of 2-amino-1,3,4-thiadiazoles in water - Peng Liu; Ao-Ze Su; Yuan-Qiang Wang; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Decreased Astroglial Monocarboxylate Transporter 4 Expression in Temporal Lobe Epilepsy - Bei Liu; Le Niu; Ming-Zhi Shen; Lei Gao; Chao Wang; Jie Li; Li-Jia Song; Ye Tao; Qiang Meng; Qian-Li Yang; Guo-Dong Gao; Hua Zhang (Molecular Neurobiology, 2014)

Relationship between post-operative cognitive dysfunction and regional cerebral oxygen saturation and β-amyloid protein - Xi-ming Li; Ming-tao Shao; Jian-juan Wang; Yue-lan Wang (Journal of Zhejiang University-SCIENCE B, 2014)

Dioxin and Dioxin-Like Compounds Suppress Acetylcholinesterase Activity via Transcriptional Downregulations In Vitro - Hai-Ming Xu; Heidi Qunhui Xie; Wu-Qun Tao; Zhi-Guang Zhou; Shuai-Zhang Li; Bin Zhao (Journal of Molecular Neuroscience, 2014)

Ephrin-B2/EphA4 forward signaling is required for regulation of radial migration of cortical neurons in the mouse - Yan Hu; Sen Li; Hua Jiang; Ming-Tao Li; Jia-Wei Zhou (Neuroscience Bulletin, 2014)

Ferulic acid prevents liver injury and increases the anti-tumor effect of diosbulbin B in vivo - Jun-ming Wang; Yu-chen Sheng; Li-li Ji; Zheng-tao Wang (Journal of Zhejiang University-SCIENCE B, 2014)

Anterolateral minithoracotomy versus median sternotomy for mitral valve disease: a meta-analysis - Chao Ding; Da-ming Jiang; Kai-yu Tao; Qun-jun Duan; Jie Li; Min-jian Kong; Zhong-hua Shen; Ai-qiang Dong (Journal of Zhejiang University-SCIENCE B, 2014)

Circulating Obestatin Levels Correlate with Fasting Insulin and HOMA-IR but Not with Hypertension in Elderly Men - Li Shao; Yin-tao Zhao; Li-li Teng; Ming-zhu Li; Hua Jiang (Cell Biochemistry and Biophysics, 2014)

Haemocyte Apoptosis of the Tiger Shrimp Penaeus monodon Exposed to Cadmium - Jian-An Xian; Bin Li; Hui Guo; Yu-Tao Miao; Jian-Min Ye; Li-Na Feng; Chao-Xia Ye; Xun-Bin Pan; An-Li Wang; Xuan-Ming Hao (Bulletin of Environmental Contamination and Toxicology, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Genetic diversity analysis of yams (Dioscorea spp.) cultivated in China using ISSR and SRAP markers - Zhi Gang Wu; Xiao Xia Li; Xin Chun Lin; Wu Jiang; Zheng Ming Tao; Nitin Mantri; Chuan Yin Fan; Xiao Qing Bao (Genetic Resources and Crop Evolution, 2014)

Resveratrol Pretreatment Attenuates the Isoflurane-Induced Cognitive Impairment Through its Anti-Inflammation and -Apoptosis Actions in Aged Mice - Xiao-min Li; Mai-tao Zhou; Xing-ming Wang; Mu-huo Ji; Zhi-qiang Zhou; Jian-jun Yang (Journal of Molecular Neuroscience, 2014)

Supramolecular Interaction of Two Tryptophans with p-sulfonated calix[4,6,8]arene - Tao-Tao Pang; Hai-Long Liu; Li-Ming Du; Yin-Xia Chang; Yun-Long Fu (Journal of Fluorescence, 2014)

Cloning, expression and stress-respondent transcription of long-chain acyl-coenzyme A synthetase cDNA gene of Nannochloropsis gaditana and its involvement in the biosynthesis of eicosapentaenoic and decosahexaenoic acids - Ming-gang Zheng; Yi-jiang Huang; Li Zheng; Zhong-tao Sun; Ling Wang (Biotechnology Letters, 2014)

Sirt1 Promotes Axonogenesis by Deacetylation of Akt and Inactivation of GSK3 - Xiao-hong Li; Chong Chen; Yue Tu; Hong-tao Sun; Ming-liang Zhao; Shi-xiang Cheng; Yang Qu; Sai Zhang (Molecular Neurobiology, 2013)

The PpLTP1 Primary Allergen Gene is Highly Conserved in Peach and Has Small Variations in Other Prunus Species - Ying-tao Ma; Xiang Zhou; Zhong-shan Gao; Xiong-wei Li; Hui-juan Jia; Hong-xia Wu; Rang-jin Xie; Zhi-qiang Wang; Ming-liang Yu; Ke Cao; Shuang-jian Chen; Ying-hui Li; et al. (Plant Molecular Biology Reporter, 2013)

Polymorphism of follicle stimulating hormone beta (FSHβ) subunit gene and its association with litter traits in giant panda - Xiaoyu Huang; Desheng Li; Jiwen Wang; Yan Huang; Chunchun Han; Guiquan Zhang; Zhi Huang; Honglin Wu; Ming Wei; Guosong Wang; Haiping Hu; Tao Deng; et al. (Molecular Biology Reports, 2013)

Combination of pharmacophore hypothesis, genetic function approximation model, and molecular docking to identify novel inhibitors of S6K1 - Hui Zhang; Ming-Li Xiang; Jun-Yu Liang; Tao Zeng; Xiao-Nuo Zhang; Ji Zhang; Sheng-Yong Yang (Molecular Diversity, 2013)

Using proteomic analysis to find the proteins involved in resistance against Sclerotinia sclerotiorum in adult Brassica napus - Li Wen; Tai-Long Tan; Jia-Bin Shu; Ying Chen; Ying Liu; Zhong-Fang Yang; Qiu-Ping Zhang; Ming-Zhi Yin; Jun Tao; Chun-Yun Guan (European Journal of Plant Pathology, 2013)

Construction and characterization of an infectious cDNA clone of enterovirus type 71 subgenotype C4 - Yong-Xin Zhang; Tao Wei; Xiao-Yu Li; Xiao Yin; Yu-Huan Li; Ji-Wei Ding; Jin-Ming Zhou; Guang-Zhou Zhang; Qi Jin; Shan Cen (Virus Genes, 2013)

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention - Min Zhang; Hao-yu Meng; Ying-ming Zhao; Zhi-wen Tao; Xiao-xuan Gong; Ze-mu Wang; Bo Chen; Zheng-xian Tao; Chun-jian Li; Tie-bing Zhu; Lian-sheng Wang; Zhi-jian Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Effects of Ethephon on Key Enzymes of Sucrose Metabolism in Relation to Sucrose Accumulation in Sugarcane - Ai-Qin Wang; Wen-Jing Huang; Jun-Qi Niu; Ming Liu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2013)

Knockout of the VPS22 component of the ESCRT-II complex in rice (Oryza sativa L.) causes chalky endosperm and early seedling lethality - Xiang-Qian Zhang; Pei Hou; Hai-Tao Zhu; Guo-Dong Li; Xin-Guo Liu; Xin-Ming Xie (Molecular Biology Reports, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Changes in the BAG1 Expression of Schwann Cells After Sciatic Nerve Crush - Hao Wu; Yonghua Liu; Yuan Zhou; Long Long; Xinghai Cheng; Lei Ji; Hai Weng; Tao Ding; Jiao Yang; Haixiang Wei; Ming Li; Weipeng Huan; et al. (Journal of Molecular Neuroscience, 2013)

Association of growth/differentiation factor 1 gene polymorphisms with the risk of congenital heart disease in the Chinese Han population - Xiaowei Sun; Ying Meng; Tao You; Peiqiang Li; Hua Wu; Ming Yu; Xiaodong Xie (Molecular Biology Reports, 2013)

Late Quaternary (30.7–9.0 cal ka BP) vegetation history in Central Asia inferred from pollen records of Lake Balikun, northwest China - Cheng-Bang An; Shi-Chen Tao; Jiaju Zhao; Fa-Hu Chen; Yanbin Lv; Weimiao Dong; Hu Li; Yongtao Zhao; Ming Jin; Zongli Wang (Journal of Paleolimnology, 2013)

Temporal and Spatial Expression of KIF3B after Acute Spinal Cord Injury in Adult Rats - Xiaowei Yu; Hai Wen; Jianhua Cao; Binbin Sun; Tao Ding; Ming Li; Hao Wu; Long Long; Xinghai Cheng; Guangfei Xu; Feng Zhang (Journal of Molecular Neuroscience, 2013)

Drug–drug interaction of rabeprazole and clopidogrel in healthy Chinese volunteers - Jia Wu; Li-Tao Jia; Li-Ming Shao; Jia-Min Chen; Dan-Dan Zhong; Song Xu; Jian-Ting Cai (European Journal of Clinical Pharmacology, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Meta-analysis of QTL associated with tolerance to abiotic stresses in barley - Wei-Tao Li; Chunji Liu; Ya-Xi Liu; Zhi-En Pu; Shou-Fen Dai; Ji-Rui Wang; Xiu-Jin Lan; You-Liang Zheng; Yu-Ming Wei (Euphytica, 2013)

Function of the anal sacs and mid-gut in mitochondrial sulphide metabolism in the echiuran worm Urechis unicinctus - Yu-Bin Ma; Zhi-Feng Zhang; Ming-Yu Shao; Kyoung-Ho Kang; Li-Tao Zhang; Xiao-Li Shi; Ying-Ping Dong (Marine Biology Research, 2012)

An efficient three-component, one-pot synthesis of 2-alkylthio-4-amino-5-cyano-6-aryl(alkyl)pyrimidines in water - Qiao-Yan Li; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2012)

Role of NOD2 in regulating the immune response to Aspergillus fumigatus - Zhuo-zhe Li; Li-li Tao; Jing Zhang; Hui-jun Zhang; Jie-Ming Qu (Inflammation Research, 2012)

Signal transduction during cold, salt, and drought stresses in plants - Guo-Tao Huang; Shi-Liang Ma; Li-Ping Bai; Li Zhang; Hui Ma; Ping Jia; Jun Liu; Ming Zhong; Zhi-Fu Guo (Molecular Biology Reports, 2012)

Isolation and identification of an acetoin high production bacterium that can reverse transform 2,3-butanediol to acetoin at the decline phase of fermentation - Xian Zhang; Tao-wei Yang; Qing Lin; Mei-juan Xu; Hai-feng Xia; Zheng-hong Xu; Hua-zhong Li; Zhi-ming Rao (World Journal of Microbiology and Biotechnology, 2011)

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro - Yi-ming Ma; Rong-ya Tao; Qian Liu; Juan Li; Jin-ying Tian; Xiao-lin Zhang; Zhi-yan Xiao; Fei Ye (Molecular and Cellular Biochemistry, 2011)

A new alkaloid from the marine-derived fungus Hypocrea virens - Tao Liu; Zhan-Lin Li; Yu Wang; Li Tian; Yue-Hu Pei; Hui-Ming Hua (Natural Product Research, 2011)

Effects of rhizobial inoculation, cropping systems and growth stages on endophytic bacterial community of soybean roots - Yun Zeng Zhang; En Tao Wang; Mao Li; Qin Qin Li; Yan Ming Zhang; Shuang Jin Zhao; Xiu Ling Jia; Li Hua Zhang; Wen Feng Chen; Wen Xin Chen (Plant and Soil, 2011)

Meta-analysis of TYK2 gene polymorphisms association with susceptibility to autoimmune and inflammatory diseases - Jin-Hui Tao; Yan-Feng Zou; Xiao-Liang Feng; Jing Li; Fang Wang; Fan-Ming Pan; Dong-Qing Ye (Molecular Biology Reports, 2011)

Fluoride-Induced Oxidative Stress in Three-Dimensional Culture of OS732 Cells and Rats - Hui Liu; Jing-chun Sun; Zhi-tao Zhao; Jin-ming Zhang; Hui Xu; Guang-sheng Li (Biological Trace Element Research, 2011)

RNA Interference Induces Effective Inhibition of mRNA Accumulation and Protein Expression of SHEV ORF3 Gene In vitro - Tao Liu; Ming Lei; Hanwei Jiao; Li Du; Ying Cheng; Donglin Zhang; Yongchang Hao; Churiga Man; Fengyang Wang (Current Microbiology, 2011)

Dynamic Changes of Heme Oxygenase-1 in the Hippocampus of Rats After Acute Carbon Monoxide Poisoning - Li Guan; Yan-Lin Zhang; Tao Wen; Xi-Fu Wang; Ming-Xia Zhu; Jin-Yuan Zhao (Archives of Environmental Contamination and Toxicology, 2011)

Identification, localization, and characterization of putative USP genes in barley - Wei-Tao Li; Yu-Ming Wei; Ji-Rui Wang; Chun-Ji Liu; Xiu-Jin Lan; Qian-Tao Jiang; Zhi-En Pu; You-Liang Zheng (Theoretical and Applied Genetics, 2010)

Distinct neural mechanisms underlying acute and repeated administration of antipsychotic drugs in rat avoidance conditioning - Ming Li; Tao Sun; Chen Zhang; Gang Hu (Psychopharmacology, 2010)

Isolation and characterization of 10 microsatellite loci for White-headed Langur (Trachypithecus leucocephalus) - Sun Tao; Wang Bo-Shi; Liu Zhi-Jin; Huang Cheng-Ming; Zhou Qi-Hai; Li Ming (Conservation Genetics Resources, 2010)

Geniposide inhibits interleukin-6 and interleukin-8 production in lipopolysaccharide-induced human umbilical vein endothelial cells by blocking p38 and ERK1/2 signaling pathways - Hong-Tao Liu; Jun-Lin He; Wen-Ming Li; Zhu Yang; Ying-Xiong Wang; Juan Yin; Yu-Guang Du; Chao Yu (Inflammation Research, 2010)

The interaction between interferon-induced protein with tetratricopeptide repeats-1 and eukaryotic elongation factor-1A - Hong-Tao Li; Yong-Ping Su; Tian-Min Cheng; Jian-Ming Xu; Jie Liao; Ji-Chuan Chen; Chang-You Ji; Guo-Ping Ai; Jun-Ping Wang (Molecular and Cellular Biochemistry, 2010)

Expression of the apoptosis-related proteins caspase-3 and NF-κB in the hippocampus of Tg2576 mice - Yan-Li Niu; Wei-Juan Zhang; Ping Wu; Bin Liu; Guo-Tao Sun; Dong-Ming Yu; Jin-Bo Deng (Neuroscience Bulletin, 2010)

Epigallocatechin-3-gallate induced primary cultures of rat hippocampal neurons death linked to calcium overload and oxidative stress - Shu-Ting Yin; Ming-Liang Tang; Hong-Min Deng; Tai-Ran Xing; Ju-Tao Chen; Hui-Li Wang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Relationships among Avena species as revealed by consensus chloroplast simple sequence repeat (ccSSR) markers - Wei-Tao Li; Yuan-Ying Peng; Yu-Ming Wei; Bernard R. Baum; You-Liang Zheng (Genetic Resources and Crop Evolution, 2009)

Arabidopsis microtubule-associated protein AtMAP65-2 acts as a microtubule stabilizer - Hua Li; Xian Zeng; Zi-Qiang Liu; Qiu-Tao Meng; Ming Yuan; Tong-Lin Mao (Plant Molecular Biology, 2009)

Opposite effects of α-lipoic acid on antioxidation and long-term potentiation in control and chronically lead-exposed rats - Hui-Li Wang; Xiang-Tao Chen; Shu-Ting Yin; Jin Liu; Ming-Liang Tang; Chuan-Yun Wu; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Quercetin relieves chronic lead exposure-induced impairment of synaptic plasticity in rat dentate gyrus in vivo - Pu Hu; Ming Wang; Wei-Heng Chen; Ji Liu; Liang Chen; Shu-Ting Yin; Wu Yong; Ju-Tao Chen; Hui-Li Wang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

The concentrations, distribution and sources of PAHs in agricultural soils and vegetables from Shunde, Guangdong, China - Yong Tao Li; Fang Bai Li; Jun Jian Chen; Guo Yi Yang; Hong Fu Wan; Tian Bin Zhang; Xiao Duo Zeng; Jian Ming Liu (Environmental Monitoring and Assessment, 2008)

Spatial distribution of leaf form and the self-thinning exponent are affected by the sensitivity of the response to abscisic acid in anArabidopsis thaliana population - Yun Wang; Jian-Ming Deng; Tao Li; Zhong-Kui Xie; Ruo-Yu Wang; Gen-Xuan Wang (Journal of Plant Biology, 2008)

Cloning and characterization of chicken SPATA4 gene and analysis of its specific expression - Ming-Chao Xie; Chao Ai; Xiu-Mei Jin; Shang-Feng Liu; Shi-Xin Tao; Zan-Dong Li; Zhao Wang (Molecular and Cellular Biochemistry, 2007)

Proteomic identification of differently expressed proteins responsible for osteoblast differentiation from human mesenchymal stem cells - Ai-Xia Zhang; Wei-Hua Yu; Bao-Feng Ma; Xin-Bing Yu; Frank Fuxiang Mao; Wei Liu; Jia-Qing Zhang; Xiu-Ming Zhang; Shu-Nong Li; Ming-Tao Li; Bruce T. Lahn; Andy Peng Xiang (Molecular and Cellular Biochemistry, 2007)

Natural hybridization origin of Rhododendron agastum (Ericaceae) in Yunnan, China: inferred from morphological and molecular evidence - Jing-Li Zhang; Chang-Qin Zhang; Lian-Ming Gao; Jun-Bo Yang; Hong-Tao Li (Journal of Plant Research, 2007)

Characterization of Soil Physico-Chemical and Microbial Parameters after Revegetation Near Shaoguan Pb/Zn Smelter, Guangdong, P.R. China - Chong-Bang Zhang; Li-Nan Huang; Ming-Hong Wong; Jin-Tao Zhang; Cheng-Jie Zhai; Chong-Yu Lan (Water, Air, & Soil Pollution, 2006)

Conversion of taxane glycosides to 10-deacetylbaccatin III - Tao Yang; Ming Li; Jian-Min Chen (Natural Product Research, 2006)

Probabilistic Analysis Indicates Discordant Gene Trees in Chloroplast Evolution - Claus Vogl; Jonathan Badger; Paul Kearney; Ming Li; Michael Clegg; Tao Jiang (Journal of Molecular Evolution, 2003)

Crystal structure studies on rubrerythrin: enzymatic activity in relation to the zinc movement - Mei Li; Ming-yih Liu; Jean LeGall; Lu-lu Gui; Jun Liao; Tao Jiang; Ji-ping Zhang; Dong-cai Liang; Wen-rui Chang (JBIC Journal of Biological Inorganic Chemistry, 2003)

Effects of Lead on 4-Aminobiphenyl Pharmacokinetics in Liver, Kidney, Spleen, Testes, Heart, Lung and Hemoglobin Adduct for Rat Model - Hui-Ming Chen; Tao Qin; Li-Xin Zhao; Xiao-Bai Xu (Ecotoxicology, 2002)

Beneficial effect of HCL-31D in murine models of endotoxaemia - Tz-Chong Chou; Chi-Yuan Li; Tzong-Ming Wu; Shang-Tao Tang; An-Rong Lee; Yu-An Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)